Chemically strengthened microcrystalline glass, cover plate glass, electronic equipment and glass device
By adjusting the composition and stress distribution structure of the crystal crystal glass, the problem of high lithium content crystal crystal glass is prone to surface cracking after chemical strengthening, and high mechanical strength and excellent damage resistance are achieved.
Patent Information
- Application Number
- CN202411386703.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
After chemical reinforcement treatment, crystallized glass with high lithium content is prone to surface cracking problems, resulting in a significant reduction in anti-fall damage properties and mechanical strength.
By adjusting the composition and stress distribution structure of the microcrystalline glass, it meets specific stress characteristics, especially the relationship between the molar percentage content of ZrO2 and the stress characteristic relationship A meets specific requirements, thereby overcoming the surface cracking problem.
It effectively overcomes the surface cracking problem of chemically strengthened microcrystalline glass, ensuring that it has high mechanical strength and excellent damage resistance.
Smart Images

Figure CN119409416A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of microcrystalline glass, and in particular to a chemically strengthened microcrystalline glass, a cover glass, an electronic device and a glass device. Background Art
[0002] As a solid material containing microcrystalline phase and glass phase, microcrystalline glass has obvious advantages in overall strength performance over ordinary glass because of the large number of tiny crystals it contains that can hinder the expansion of microcracks. At present, microcrystalline glass has begun to be used in electronic devices, for example, as cover glass for portable electronic devices. For another example, the application of microcrystalline glass includes but is not limited to display cover, back cover, camera protection cover, etc.
[0003] Common crystalline phases in glass-ceramics include lithium monosilicate, lithium disilicate, petalite, quartz, quartz solid solution, spinel, spodumene, nepheline, zirconium oxide, and the like. Among them, lithium disilicate (Li2Si2O5) is an orthorhombic crystal based on the [Si2O5] tetrahedral array, and the shape of the crystal is flat or plate-like. Inside the glass-ceramics, lithium disilicate crystals are often randomly oriented interlocking microstructures, which can force the crack path to be distorted when passing through the crystal, thereby preventing the crack from expanding and improving the strength and fracture toughness of the glass-ceramics. At the same time, lithium disilicate crystals are also ideal crystal phases for preparing highly transparent glass-ceramics. Therefore, glass-ceramics with lithium disilicate as the main crystal phase have great application potential in the cover glass market for electronic devices.
[0004] As cover glass for electronic devices, especially for portable electronic devices (such as mobile phones, tablets, smart watches, smart bracelets, etc.), in addition to strength, it is also expected that the microcrystalline glass used as cover glass in portable electronic devices is as thin as possible. In order to make the microcrystalline glass as thin as possible obtain high strength performance so that it can better cope with problems such as extrusion, impact, scratches, and wear, it is usually necessary to chemically strengthen the microcrystalline glass.
[0005] Since lithium is an essential component of the lithium disilicate crystal phase, and lithium ions are the key ions for ion exchange in lithium disilicate glass-ceramics during the chemical strengthening process, in order to obtain lithium disilicate glass-ceramics that can be strengthened and have a high crystalline phase content, while ensuring that the strengthened glass-ceramics obtains a high stress level, it is usually considered to add a large amount of lithium to the glass composition. Summary of the invention
[0006] Without being limited by any theory, when a glass-ceramic with a high lithium content and lithium disilicate as the main crystal phase is chemically strengthened in a molten salt bath, especially in a high-temperature molten salt bath, a large number of irregular cracks / cracks are easily formed on the surface of the chemically strengthened glass-ceramic. These cracks / cracks exist on the surface of the chemically strengthened glass-ceramic, with a depth of 10μm to 100μm, hereinafter referred to as "surface cracking". The "surface cracking" problem of chemically strengthened glass-ceramic will greatly reduce the drop damage resistance and mechanical strength of the chemically strengthened glass-ceramic. More seriously, it may even cause the surface of the chemically strengthened glass-ceramic to fail directly due to too many cracks / cracks and cannot be used.
[0007] Furthermore, the inventors discovered that when chemically strengthening a glass-ceramic with a high lithium content and lithium disilicate as the main crystal phase to prepare a chemically strengthened glass-ceramic with desired properties, the compatibility between the glass composition and the stress distribution structure is very important. If the two are not compatible, the problem of "surface cracking" of the chemically strengthened glass-ceramic will easily occur, resulting in a significant reduction in the mechanical strength performance of the chemically strengthened glass-ceramic. When a glass-ceramic with a specific composition is matched to a suitable and better stress distribution structure, not only can the problem of "surface cracking" of the chemically strengthened glass-ceramic be overcome, but also the high mechanical strength performance of the chemically strengthened glass-ceramic can be ensured.
[0008] The present application provides a chemically strengthened glass-ceramic and a cover glass, an electronic device and a glass device comprising the chemically strengthened glass-ceramic. The chemically strengthened glass-ceramic has a high lithium content, with lithium disilicate as the main crystal phase, and has a specific composition and a specific stress distribution structure, so that the chemically strengthened glass-ceramic not only does not have the problem of "surface cracking", but also has high mechanical strength performance.
[0009] Specifically, the technical solutions provided by this application include:
[0010] In a first aspect, a chemically strengthened glass-ceramic is provided, wherein the main crystalline phase of the chemically strengthened glass-ceramic is a lithium disilicate crystalline phase; the crystallinity of the chemically strengthened glass-ceramic is not less than 65%; and the Li2O content at the center of the chemically strengthened glass-ceramic is not less than 11% in terms of the mass percentage of the oxide;
[0011] The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside; the chemically strengthened glass-ceramics satisfies the following relationship:
[0012]
[0013] B=A-83989×n(ZrO2) 2+2526.5×n(ZrO2), 130≤B≤180, preferably, 135≤B≤180, more preferably 135≤B≤175;
[0014] Where t is the depth from the main surface of the chemically strengthened glass-ceramics, CS(t) is the compressive stress value at the depth t, is the stress integral of the compressive stress layer from the main surface of the chemically strengthened glass-ceramics to DOL_0, in MPa·μm;
[0015] DOL_0 is the depth of the compressive stress layer, in μm;
[0016] In relational formula A, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained. The unit does not participate in the calculation;
[0017] n(ZrO2) is the molar percentage content of ZrO2 at the center of the chemically strengthened glass-ceramics;
[0018] In relational expression B, the numerical value of relational expression A and the numerical value of the molar percentage content of ZrO2 are substituted into the calculation to obtain the calculation result, and the unit is not involved in the calculation.
[0019] The present application makes a high-lithium-content microcrystalline glass with a specific composition and lithium disilicate as the main crystal phase meet specific stress characteristics after chemical strengthening treatment. In particular, the relationship A between the molar percentage content of ZrO2 in the microcrystalline glass and the stress characteristics meets specific requirements (that is, meets the range requirements of the aforementioned relationship B). This can not only effectively overcome the problem of "surface cracking" of the chemically strengthened microcrystalline glass, but also ensure that the chemically strengthened microcrystalline glass has high mechanical strength properties, and thus ensure that the chemically strengthened microcrystalline glass has excellent damage resistance.
[0020] In some embodiments of the present application, the value of the relational expression A satisfies: 120≤A≤250, preferably, 130≤A≤240, and more preferably, 130≤A≤235. By making the chemically strengthened glass-ceramics satisfy the relational expression A, it is beneficial for the chemically strengthened glass-ceramics to obtain a desired high stress level, thereby facilitating ensuring that the chemically strengthened glass-ceramics has high mechanical strength properties.
[0021] In some embodiments of the present application, the value of relational formula A is: 150.39, 155.13, 157.8, 163.95, 165.23, 167.78, 171.98, 130.02, 148.08, 153.52, 157.87, 150.70, 161.51, 200.59, 217.59, 234.24, 208.06, 207.14, 220.07, 224.21 or 226.66; and / or,
[0022] The value of relational expression B is: 144.41, 149.14, 151.82, 157.96, 159.24, 161.80, 166.00, 148.99, 165.83, 168.65, 170.67, 163.85, 155.53, 136.18, 155.43, 172.09, 147.01, 147.17, 165.17, 164.24 or 166.69.
[0023] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: C=A-|CT_AV|, 30≤C≤90, preferably, 30≤C≤85, more preferably, 30≤C≤80, wherein |CT_AV| is the absolute value of the average tensile stress, in MPa. By making the chemically strengthened glass-ceramics satisfy the relationship C, it is helpful to overcome the problem of "surface cracking" of the obtained chemically strengthened glass-ceramics and to ensure that the chemically strengthened glass-ceramics has high mechanical strength properties.
[0024] In some embodiments of the present application, the value of relational formula C is: 33.97, 40.28, 37.3, 41.41, 47.67, 42.93, 45.51, 45.77, 52.74, 53.28, 51.42, 52.28, 37.27, 64.74, 70.95, 77.45, 57.85, 52.49, 67.32, 66.26 or 64.31.
[0025] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: 2.0≤|K 0.5×DOL_0 |≤6.0, where |K 0.5×DOL_0 |The absolute value of the slope of the stress curve when the depth from the main surface of the chemically strengthened micro-ceramic glass is t=0.5×DOL_0.
[0026] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0≤M(K2O)≤1.5%, 5%≤M(Na2O)≤25%; M(K2O) is the mass percentage of K2O on the surface of the chemically strengthened glass-ceramics, and M(Na2O) is the mass percentage of Na2O on the surface of the chemically strengthened glass-ceramics.
[0027] In some embodiments of the present application, after the two main surfaces of the chemically strengthened microcrystalline glass are thinned by 3 μm each, the obtained chemical microcrystalline glass satisfies: the mass percentage of K2O M'(K2O) on the surface of the chemical microcrystalline glass and the mass percentage of Na2O M'(Na2O) on the surface of the chemical microcrystalline glass are: 0≤M'(K2O)≤0.5%, 4.0%≤M'(Na2O)≤20%.
[0028] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mole percentage of oxides, comprises:
[0029] SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 3%, ZrO2: 1% to 6%, Li2O: 24% to 32%. In the present application, by adjusting and controlling the content range of each oxide component, it is beneficial to ensure that the chemically strengthened microcrystalline glass that meets the desired crystal phase structure and stress structure is obtained.
[0030] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, further includes: SrO: 0% to 3%, and / or, Na2O: 0% to 4%, and / or, K2O: 0% to 2%, and / or, CaO: 0% to 5%, and / or, B2O3: 0% to 1%, and / or, Ta2O5: 0% to 1%, and / or, BaO: 0% to 3%, and / or, MgO: 0% to 3%, and / or, ZnO: 0% to 3%, and / or, Y2O3: 0% to 1%, and / or, La2O3: 0% to 1%, and / or, Yb2O3: 0% to 1%.
[0031] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mole percentage of oxides, comprises:
[0032] The molar percentage of SiO2 is 60% to 65%, preferably 60.5% to 64.50%; and / or,
[0033] The molar percentage of Al2O3 is 0.5% to 3.5%, preferably 1% to 1.5%; and / or,
[0034] The molar percentage of P2O5 is 1% to 2.8%, preferably 1.20% to 2%; and / or,
[0035] The molar percentage of ZrO2 is 1% to 5%, preferably 1.4% to 5%; and / or,
[0036] The molar percentage of Li2O is 24% to 31.6%, preferably 27.5% to 31%; and / or,
[0037] The molar percentage of Na2O is 0% to 3%, preferably 0% to 1%; and / or,
[0038] The molar percentage of K2O is 0% to 1%, preferably 0% to 0.7%; and / or,
[0039] The molar percentage of CaO is 0% to 4%, preferably 0% to 3%; and / or,
[0040] The molar percentage of BaO is 0% to 2%, preferably 1% to 2%; and / or,
[0041] The molar percentage of SrO is 0% to 2%, preferably 1% to 2%; and / or,
[0042] The molar percentage of MgO is 0% to 2%; and / or,
[0043] The molar percentage of ZnO is 0% to 2%; and / or,
[0044] The molar percentage of B2O3 is 0% to 0.7%, preferably 0% to 0.5%; and / or,
[0045] The molar percentage of Y2O3 is 0% to 0.5%, preferably 0% to 0.2%; and / or,
[0046] The molar percentage of La2O3 is 0% to 0.5%, preferably 0% to 0.2%; and / or,
[0047] The molar percentage of Ta2O5 is 0% to 0.7%, preferably 0% to 0.5%; and / or,
[0048] The molar percentage of Yb2O3 is 0% to 0.7%, preferably 0% to 0.5%.
[0049] In the present application, the appropriate addition of alkaline earth metal oxides such as BaO, SrO, MgO, and CaO is beneficial to improving the glass melting process, making it difficult to crystallize during the glass melting process, and is beneficial to reducing the high temperature viscosity to a certain extent, increasing the density of the substrate glass, increasing the Young's modulus, and also to a certain extent making the glass obtain higher stress after strengthening. The appropriate addition of rare earth metal oxides such as Y2O3, La2O3, and Yb2O3 can increase the density of the substrate glass and improve the Young's modulus of the microcrystalline glass. The appropriate addition of transition metal oxides such as Ta2O5 can increase the density of the substrate glass and improve the Young's modulus of the microcrystalline glass. The appropriate addition of alkali metal oxides such as Na2O and K2O can play a role in improving the glass melting process, but will reduce the stress of chemically strengthened microcrystalline glass.
[0050] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics comprises, in terms of molar percentage of oxides:
[0051] The molar percentage of SiO2 is 60.92%, 60.94%, 61.15%, 61.16%, 61.43%, 61.72%, 61.82%, 62.58%, 62.77%, 63.16%, 63.39% or 63.86%; and / or,
[0052] The molar percentage of Al2O3 is 1.14%, 1.22%, 1.23%, 1.37%, 1.38%, 1.4%, 1.42%, 1.43% or 1.44%; and / or,
[0053] The molar percentage of P2O5 is 1.51%, 1.74%, 1.83%, 1.84%, 1.85%, 1.86%, 1.87%, 1.89% or 1.92%; and / or,
[0054] The molar percentage of ZrO2 is 1.44%, 1.89%, 2.18%, 2.34%, 2.36%, 3.23%, 4.47%, 4.57%, 4.59%, 4.61% or 4.66%; and / or,
[0055] The molar percentage of Li2O is 27.54%, 29.25%, 29.38%, 29.52%, 29.8%, 30.22%, 30.4%, 30.44%, 30.81% or 31.51%; and / or,
[0056] The molar percentage of Na2O is 0% or 0.3%; and / or,
[0057] The molar percentage of K2O is 0% or 0.46%; and / or,
[0058] The molar percentage of CaO is 0%, 0.92% or 2.67%; and / or,
[0059] The molar percentage of BaO is 0%, 0.91%, 1.38% or 1.83%; and / or,
[0060] The molar percentage of SrO is 0%, 0.91%, 0.92%, 1.38%, 1.42% or 1.83%; and / or,
[0061] The molar percentage of MgO is 0%, 0.2% or 1.83%; and / or,
[0062] The molar percentage of ZnO is 0%, 0.54% or 1.67%; and / or,
[0063] The molar percentage of B2O3 is 0% or 0.46%; and / or,
[0064] The molar percentage of Y2O3 is 0% or 0.2%, and / or,
[0065] The molar percentage of La2O3 is 0% or 0.2%; and / or,
[0066] The molar percentage of Ta2O5 is 0%, 0.46% or 0.5%; and / or,
[0067] The molar percentage of Yb2O3 is 0% or 0.46%.
[0068] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0069] 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20, wherein n(SiO2) and n(Li2O) are the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0070] 90%≤n(SiO2)+n(Li2O)≤96%, preferably, 90%≤n(SiO2)+n(Li2O)≤95%, wherein n(SiO2) and n(Li2O) are respectively the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics; and / or,
[0071] 20%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, preferably, 25%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, wherein n(Li2O), n(ZrO2), and n(CaO) are the molar percentage contents of Li2O, ZrO2, and CaO at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0072] 0%≤n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤1%, preferably, 0%≤n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤0.7%, wherein n(Y2O3), n(La2O3), n(Ta2O5), and n(Yb2O3) are the molar percentage contents of Y2O3, La2O3, Ta2O5, and Yb2O3 at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0073] 0%≤n(SrO)+n(BaO)+n(CaO)+n(MgO)≤3%, preferably, 0%≤n(SrO)+n(BaO)+n(CaO)+n(MgO)≤2.7%, wherein n(SrO), n(BaO), n(CaO), n(MgO) are the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0074] 0≤n(SrO) / [n(SrO)+n(BaO)+n(CaO)+n(MgO)]≤1, wherein n(SrO), n(BaO), n(CaO), and n(MgO) are the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened microcrystalline glass, respectively. In the present application, by adjusting and controlling the content relationship of each oxide, it is beneficial to ensure that a microcrystalline glass that meets the desired performance and has lithium disilicate as the main crystalline phase structure is obtained, and at the same time, it is beneficial to achieve a desired stress distribution structure.
[0075] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0076] The value of n(SiO2) / n(Li2O) is 2.01, 2.03, 2.07, 2.08, 2.09, 2.10 or 2.28, wherein n(SiO2) and n(Li2O) are the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0077] The value of n(SiO2)+n(Li2O) is 90.17%, 90.19%, 90.31%, 90.4%, 90.41%, 90.81%, 91.24%, 91.62%, 92.16%, 93.38%, 93.39%, 94.26% or 94.9%, wherein n(SiO2) and n(Li2O) are the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0078] The value of 2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO) is 29.39%, 29.77%, 30.05%, 42.65%, 43.99%, 50.6%, 52.02%, 52.88% or 56.88%, wherein n(Li2O), n(ZrO2) and n(CaO) are the molar percentage contents of Li2O, ZrO2 and CaO at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0079] The value of n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3) is 0%, 0.2%, 0.46% or 0.7%, wherein n(Y2O3), n(La2O3), n(Ta2O5) and n(Yb2O3) are the molar percentage contents of Y2O3, La2O3, Ta2O5 and Yb2O3 at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0080] The value of n(SrO)+n(BaO)+n(CaO)+n(MgO) is 0%, 0.2%, 0.92%, 1.38%, 1.42%, 1.83% or 2.67%, wherein n(SrO), n(BaO), n(CaO) and n(MgO) are the molar percentage contents of SrO, BaO, CaO and MgO at the center of the chemically strengthened glass-ceramics, respectively; and / or,
[0081] The value of n(SrO) / [n(SrO)+n(BaO)+n(CaO)+n(MgO)] is 0, 0.5 or 1, wherein n(SrO), n(BaO), n(CaO) and n(MgO) are the molar percentage contents of SrO, BaO, CaO and MgO at the center of the chemically strengthened glass-ceramics, respectively.
[0082] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in terms of mass percentage of oxides, comprises:
[0083] SiO2: 55% to 75%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 3% to 12%, Li2O: 11% to 20%.
[0084] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in mass percentage of oxides, further includes: SrO: 0% to 6%, and / or, Na2O: 0% to 4%, and / or, K2O: 0% to 2%, and / or, CaO: 0% to 5%, and / or, B2O3: 0% to 1%, and / or, Ta2O5: 0% to 2%, and / or, BaO: 0% to 6%, and / or, MgO: 0% to 3%, and / or, ZnO: 0% to 3%, and / or, Y2O3: 0% to 2%, and / or, La2O3: 0% to 2%, and / or, Yb2O3: 0% to 4%.
[0085] In some embodiments of the present application, the composition at the center of the chemically strengthened glass-ceramics, measured in terms of mass percentage of oxides, comprises:
[0086] The mass percentage of SiO2 is 60% to 71%, preferably 62% to 68%; and / or,
[0087] The mass percentage of Al2O3 is 1% to 6%, preferably 1% to 3%, more preferably 2% to 3%; and / or,
[0088] The mass percentage of P2O5 is 3% to 6%, preferably 3.5% to 5.5%; and / or,
[0089] The mass percentage of ZrO2 is 4% to 11%, preferably 4% to 10%; and / or,
[0090] The mass percentage of Li2O is 11% to 18%, preferably 12% to 17.5%, more preferably 14% to 17%; and / or,
[0091] The mass percentage of Na2O is 0% to 2.8%, preferably 0% to 1%; and / or,
[0092] The mass percentage of K2O is 0% to 1.5%, preferably 0% to 1%; and / or,
[0093] The mass percentage of CaO is 0% to 3%, preferably 0% to 1%; and / or,
[0094] The mass percentage of BaO is 0% to 5.5%, more preferably 0% to 5%; and / or,
[0095] The mass percentage of SrO is 0% to 5%, preferably 0% to 3.5%; and / or,
[0096] The mass percentage of MgO is 0% to 2%; and / or,
[0097] The mass percentage of ZnO is 0% to 2.5%; and / or,
[0098] The mass percentage of B2O3 is 0% to 0.8%, preferably 0% to 0.5%; and / or,
[0099] The mass percentage of Y2O3 is 0% to 1%, preferably 0% to 0.8%; and / or,
[0100] The mass percentage of La2O3 is 0% to 1.5%, preferably 0% to 1%; and / or,
[0101] The mass percentage of Ta2O5 is 0% to 1.5%, preferably 0% to 0.5%; and / or,
[0102] The mass percentage of Yb2O3 is 0% to 3.5%, preferably 0% to 3%.
[0103] In some embodiments of the present application, the chemically strengthened glass-ceramics has a crystallinity of 70% to 90%, more preferably, the chemically strengthened glass-ceramics has a crystallinity of 70% to 87%; and / or,
[0104] In the chemically strengthened glass-ceramics, the average grain size does not exceed 100 nm, preferably, the average grain size does not exceed 50 nm, and more preferably, the average grain size is 15 nm to 30 nm; and / or,
[0105] In the chemically strengthened glass-ceramics, the mass of lithium disilicate crystal phase accounts for 80wt% to 100wt% of all crystal phases; and / or,
[0106] The mass percentage of the petalite crystalline phase in the chemically strengthened microcrystalline glass is less than or equal to 10%, preferably less than or equal to 5%, and more preferably, does not contain the petalite crystalline phase. The present application helps the microcrystalline glass to maintain excellent optical properties while satisfying excellent mechanical strength properties and high intrinsic strength by making the microcrystalline glass meet the desired crystallinity and / or desired crystal phase composition and / or appropriate average grain size.
[0107] In some embodiments of the present application, when the thickness is not more than 0.70 mm, the b value of the chemically strengthened glass-ceramics is less than 1.0, preferably, the b value is less than 0.8, and more preferably, the b value is ≤ 0.6; and / or,
[0108] The chemically strengthened microcrystalline glass is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened microcrystalline glass is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.27%. Chemically strengthened microcrystalline glass that meets the b value and / or transmittance can ensure good display effect and transparency effect, and is suitable for use in electronic device display screens that require display effect.
[0109] In some embodiments of the present application, the Young's modulus of the chemically strengthened glass-ceramics is greater than 100 GPa, preferably, the Young's modulus is greater than 105 GPa, and more preferably, the Young's modulus is 110 GPa to 130 GPa; and / or,
[0110] The density of the chemically strengthened glass-ceramics is 2.51 g / cm 3 ~2.65g / cm 3 and / or,
[0111] The refractive index of the chemically strengthened glass-ceramics is ≤1.60, preferably, the refractive index is 1.54 to 1.60; and / or,
[0112] The thickness T of the chemically strengthened glass-ceramics is 0.35 mm to 1.0 mm, preferably, the thickness T is 0.4 mm to 0.7 mm, and more preferably, the thickness T is 0.45 mm to 0.55 mm; and / or,
[0113] The chemically strengthened glass-ceramics are 2D, 2.5D, 3D or special-shaped; and / or, the chemically strengthened glass-ceramics are of equal thickness or unequal thickness. The Young's modulus, density, and refractive index are within the above ranges, indicating that the chemically strengthened glass-ceramics have high intrinsic strength / inherent strength, which is conducive to achieving excellent mechanical strength performance and excellent damage resistance.
[0114] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies:
[0115] 0.20≤DOL_0 / T≤0.25, preferably, 0.21≤DOL_0 / T≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and T is the thickness of the chemically strengthened glass-ceramics; and / or,
[0116] 90.00 μm≤DOL_0≤160.00 μm, preferably, 100.00 μm≤DOL_0≤160.00 μm, wherein DOL_0 is the depth of the compressive stress layer; and / or,
[0117] 100.00MPa≤CS_50≤300.00MPa, preferably, 110.00MPa≤CS_50≤250.00MPa, more preferably, 110.00MPa≤CS_50≤240.00MPa, wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass; and / or,
[0118] 80.00MPa≤|CT_AV|≤200.00MPa, preferably, 80.00MPa≤|CT_AV|≤170.00MPa, more preferably, 80.00MPa≤|CT_AV|≤160.00MPa, wherein |CT_AV| is the absolute value of the average tensile stress; and / or,
[0119] 40000.00MPa / mm≤CT_LD≤100000.00MPa / mm, preferably, 47000.00MPa / mm≤CT_LD≤95000.00MPa / mm, wherein CT_LD refers to the tensile stress linear density. The present application facilitates obtaining chemically strengthened glass-ceramics with a high stress level by making the chemically strengthened glass-ceramics meet appropriate stress characteristics, thereby facilitating the improvement of mechanical strength properties by stress characteristics, and ensuring that the chemically strengthened glass-ceramics have no "surface cracking" problem, so that the chemically strengthened glass-ceramics meet excellent damage resistance.
[0120] In some embodiments of the present application, the chemically strengthened glass-ceramics is subjected to a sandpaper drop resistance test, and the sandpaper used is 80-mesh sandpaper. When the thickness does not exceed 0.70 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.0 m, preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.2 m, and more preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.6 m. The larger the measured average sandpaper drop resistance height value, the better the drop damage resistance of the chemically strengthened glass-ceramics.
[0121] In a second aspect, a glass device is provided, wherein the glass device comprises the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0122] In a third aspect, a cover glass is provided, the cover glass comprising the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect. The cover glass may be a display cover, a back cover or a camera protection cover of an electronic device.
[0123] In a fourth aspect, an electronic device is provided, the electronic device comprising the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0124] In some embodiments of the present application, the electronic device includes a housing assembled on the outside of the electronic device, and the housing includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0125] In some embodiments of the present application, the housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0126] In some embodiments of the present application, the housing includes a back cover assembled on the back side of the electronic device, and the back cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0127] In some embodiments of the present application, the electronic device also includes a camera assembly located inside the housing, the housing includes a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0128] In some embodiments of the present application, the electronic device further includes a middle frame located between the display module and the housing, and the middle frame includes the chemically strengthened microcrystalline glass as described in any embodiment of the first aspect.
[0129] In some embodiments, the housing may be partially or entirely made of chemically strengthened glass-ceramics. The electronic device in the present application may be a display cover, a back cover, a camera protection cover, or a middle frame, wherein one or more of the above may be made of chemically strengthened glass-ceramics as described in any embodiment of the first aspect.
[0130] One or more of the above technical solutions provided by the present application have the following advantages compared with the prior art:
[0131] The present application makes a high-lithium-content microcrystalline glass with a specific composition and lithium disilicate as the main crystal phase meet specific stress characteristics after chemical strengthening treatment. In particular, the relationship A between the molar percentage content of ZrO2 in the microcrystalline glass and the stress characteristics meets specific requirements (that is, meets the range requirements of the aforementioned relationship B). This can not only effectively overcome the problem of "surface cracking" of the chemically strengthened microcrystalline glass, but also ensure that the chemically strengthened microcrystalline glass has high mechanical strength properties, and thus ensure that the chemically strengthened microcrystalline glass has excellent damage resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0132] The accompanying drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application. It should be understood that the following drawings only illustrate certain embodiments of the present application and therefore should not be considered to limit the scope of the present application.
[0133] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0134] Figure 1 This is a real photo of the chemically strengthened glass-ceramics of Example 1 of the present application under strong light;
[0135] Figure 2 This is a physical photo of the chemically strengthened glass-ceramics of Comparative Example 5 of the present application under strong light;
[0136] Figure 3 This is a 2D microscopic picture of the main surface of the chemically strengthened glass-ceramics of Example 1 of the present application, magnified 200 times;
[0137] Figure 4 This is a 2D microscopic picture of the main surface of the chemically strengthened glass-ceramics of Comparative Example 5 of the present application, magnified 100 times;
[0138] Figure 5 This is a 2D microscopic picture of the cross section of the chemically strengthened glass-ceramics of Example 1 of the present application after being broken, magnified 200 times along the thickness direction;
[0139] Figure 6 This is a 2D microscopic picture of the cross section of the chemically strengthened glass-ceramics of Comparative Example 5 of the present application after being broken, magnified 200 times along the thickness direction;
[0140] Figure 7This is a schematic diagram of the test position of the sample in the embodiment of the present application using SLP-2000 to test stress. The test point is located in the center of the sample. In the figure, 7-a is the edge of the main surface of the sample, 7-b is the main surface area of the sample, and 7-c is the stress test point location area;
[0141] Figure 8 Schematic diagram of the test position of the comparative sample of this application using SLP-2000 to test stress. The test point is located in the center of the sample, and there is no "surface cracking" problem at the test point. Among them, 8-a is the edge of the main surface of the sample, 8-b is the "surface cracking" area of the sample, 8-c is the stress test point location area, and 8-d is the area of the sample without "surface cracking";
[0142] Fig. 9 is an optical transmittance curve of the chemically strengthened glass-ceramics of Example 1 of the present application within the visible light wavelength range;
[0143] Fig.10 The XRD pattern of the glass-ceramics of Example 1 of the present application;
[0144] Fig.11 : is the XRD comparison spectrum of the micro-ceramic glass before and after chemical strengthening of Example 1 of the present application, wherein A0 is the XRD spectrum of the micro-ceramic glass before chemical strengthening, and A1 is the XRD spectrum of the chemically strengthened micro-ceramic glass obtained after chemical strengthening;
[0145] Fig.12 The XRD comparison graphs of the glass-ceramics of Comparative Example 5 of the present application before and after chemical strengthening, wherein B0 is the XRD graph of the glass-ceramics before chemical strengthening, and B1 is the XRD graph of the chemically strengthened glass-ceramics obtained after chemical strengthening;
[0146] Fig.13 This is a stress distribution diagram of the chemically strengthened glass-ceramics of Example 15 of the present application tested by SLP-2000;
[0147] Fig.14 This is a stress distribution diagram of the chemically strengthened glass-ceramics of Comparative Example 8 of the present application tested by SLP-2000;
[0148] Fig.15 This is a schematic diagram of the front structure of the electronic device mentioned in the embodiment of the present application;
[0149] Fig.16 A schematic diagram of the rear structure of the electronic device mentioned in the embodiment of the present application;
[0150] Fig.17 The structure of the electronic device mentioned in the embodiment of this application is schematically shown. Figure 1 ;
[0151] Fig.18The structure of the electronic device mentioned in the embodiment of this application is schematically shown. Figure 2 ;
[0152] Fig.19 Schematic diagram of the structure of the chemically strengthened glass-ceramics of the present application, wherein d is the depth of the compressive stress layer, 21 is the compressive stress layer, and 22 is the tensile stress layer.
[0153] Figure numerals: 1-housing; 11-display screen cover; 12-back cover; 13-camera protection cover; 2-camera assembly; 3-middle frame; 4-display module. DETAILED DESCRIPTION
[0154] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0155] The endpoints and any values of the ranges disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all refer to including or not including (or may have or may not have). "And / or" as referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0156] Explanation of terms and test methods:
[0157] In this application, the phenomenon of "surface cracking" refers to the phenomenon that chemically strengthened glass (such as chemically strengthened microcrystalline glass) shows obvious cracks / cracks on the surface under strong light. The depth of the microcracks / cracks is a few microns to tens of microns, and does not penetrate the entire thickness of the glass.
[0158] In the present application, glass-ceramics is a type of solid composite material that is prepared by targeted controlled heat treatment of substrate glass and contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystal phase). Glass-ceramics are also called glass ceramics or crystallized glass.
[0159] In the present application, chemically strengthened glass-ceramics refers to a solid composite material obtained after chemical strengthening treatment of glass-ceramics. It should be understood that during chemical strengthening treatment, alkali metal ions with large ionic radius (such as potassium ions or sodium ions) in the molten salt bath (or also called molten salt bath) will replace alkali metal ions with small ionic radius (such as sodium ions or lithium ions) in the glass-ceramics, thereby generating an exchange ion volume difference and generating compressive stress (or also called compressive stress) on the surface of the glass-ceramics.
[0160] In the present application, substrate glass (or also referred to as base glass) refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.
[0161] In the present application, nucleation treatment refers to growing crystal nuclei in the substrate glass by heat treatment; crystallization treatment refers to precipitating target crystals or crystalline phases in the substrate glass by heat treatment.
[0162] In the present application, the composition at the center of the chemically strengthened glass-ceramics refers to the composition at the center of the depth or thickness of the chemically strengthened glass-ceramics or near the center of the depth or thickness, that is, the composition of the region in the chemically strengthened glass-ceramics where ion exchange has not been performed. It should be understood that the composition at the center of the chemically strengthened glass-ceramics is the same or substantially the same as the composition of the glass-ceramics used to prepare the chemically strengthened glass-ceramics but which has not yet been chemically strengthened.
[0163] In the present application, the visible light wavelength range refers to 360nm to 740nm.
[0164] In the present application, the main crystalline phase (or also referred to as the main crystalline phase) refers to a crystalline phase having a higher mass content (or also referred to as weight percentage, mass percentage) than other crystalline phases present in the microcrystalline glass or chemically strengthened microcrystalline glass.
[0165] In the present application, the main surface refers to the surface with the largest surface area, such as the upper surface or lower surface of a horizontally placed microcrystalline glass sheet.
[0166] In the present application, crystallinity refers to the percentage of the total mass of the crystalline phase in the microcrystalline glass or chemically strengthened microcrystalline glass to the mass of the microcrystalline glass or chemically strengthened microcrystalline glass, or is also called the total content of the crystalline phase in the microcrystalline glass or chemically strengthened microcrystalline glass.
[0167] In the present application, when light of a certain wavelength is irradiated onto the main surface of microcrystalline glass or chemically strengthened microcrystalline glass, the light will be reflected, absorbed and transmitted, and the ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.
[0168] In this application, the refractive index refers to the ratio of the propagation speed of light in a vacuum to the propagation speed of light in the medium.
[0169] In the present application, the crystallized glass raw material refers to the glass raw material which has reached a certain degree of crystallinity after a period of heat treatment, but has not yet reached the target crystallinity, and can continue to crystallize to reach the target crystallinity when heated.
[0170] In this application, CT_LD refers to the tensile stress linear density, with the unit of MPa / mm. In this application, CT_LD is calculated by the following formula:
[0171]
[0172] Wherein, T is the thickness of chemically strengthened glass-ceramics, in mm; DOL_0 is the depth of the compressive stress layer of chemically strengthened glass-ceramics, in μm; |CT_AV| is the absolute value of the average tensile stress of chemically strengthened glass-ceramics, in MPa. It should be understood that in the calculation formula of tensile stress linear density, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained, and the unit does not participate in the calculation.
[0173] It should be understood that after the glass-ceramics is placed in a molten salt bath for ion exchange, a compressive stress layer (or also called a compressive stress layer) will be formed on the surface of the glass-ceramics, and a tensile stress layer (or also called a tensile stress layer) will be formed inside the glass-ceramics. Exemplarily, during the chemical strengthening treatment, the alkali metal ions with a large radius in the molten salt bath are ion-exchanged with the alkali metal ions with a small radius in the glass-ceramics, thereby forming a compressive stress layer on the surface of the glass-ceramics and a tensile stress layer inside the glass-ceramics, that is, after the chemical strengthening treatment of the glass-ceramics, a chemically strengthened glass-ceramics containing a compressive stress layer and a tensile stress layer is prepared.
[0174] In the present application, CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass, in MPa, obtained by testing with an SLP-2000 stress meter (or also known as a scattered light photoelastic stress meter).
[0175] In this application, |CT_AV| refers to the absolute value of the average tensile stress, in MPa, specifically the absolute value of the average value of all tensile stresses in the tensile stress layer, obtained by testing with an SLP-2000 stress meter.
[0176] In this application, DOL_0 refers to the depth of the compressive stress layer, or the depth of the compressive stress layer, specifically the distance from any main surface of the chemically strengthened microcrystalline glass to the position where the compressive stress close to the surface is zero, obtained by testing with an SLP-2000 stress meter.
[0177] In the present application, the test method of the aforementioned stress performance is as follows: use SLP-2000 stress meter for testing, the wavelength of the light source is 518nm, SOC=25.5 (nm / cm) / MPa, the refractive index is set according to the refractive index value of the sample to be tested, and the exposure time is 300usec. When testing the stress performance of chemically strengthened microcrystalline glass, it is necessary to first drop conductive liquid on the stress meter, and then wipe the chemically strengthened microcrystalline glass sample to be tested clean, place it on the test path, and test its stress value. Among them, the stress meter is SLP-2000 and the conductive liquid used is a conductive liquid with a refractive index of 1.51. Then, the tensile stress line density (CT_LD) value of the chemically strengthened microcrystalline glass is calculated by the aforementioned tensile stress line density calculation formula; the stress data of the chemically strengthened microcrystalline glass measured by SLP-2000 is calculated. The test position refers to Figure 7 and Figure 8 .
[0178] In this application, the b value is used to characterize the yellow-blue value of a material. The b value in this application is the b value of transmitted light, and a positive b value indicates that the material is blue.
[0179] In the present application, the upper crystallization temperature limit refers to the highest temperature at which the substrate glass produces crystallization. Above this temperature, the substrate glass will not precipitate crystals.
[0180] In this application, the thickness is obtained by micrometer testing. It should be understood that in the thickness direction of the glass-ceramic sample, the degree of ion exchange changes gradually from the surface to the center, and the overall Na-K and / or Li-Na exchange amount increment (mass) generally does not exceed 1.5% of the total mass of the sample. Therefore, the expansion effect in the thickness direction is extremely slight, and it can be approximately considered that the thickness has basically not changed. That is, before and after chemical strengthening, the thickness of the glass-ceramic changes very little, which can be basically ignored, and the thickness of the glass-ceramic is basically the same as the thickness of the chemically strengthened glass-ceramic obtained therefrom.
[0181] In this application, the size specifications of the microcrystalline glass sheet are tested using a two-dimensional measuring machine (the instrument model is Miyu MY-YXCL-4030).
[0182] In this application, Young's modulus is used to characterize the ability of glass to resist elastic deformation due to external force. This application uses UMS-100 ultrasonic material characterization system to test the Young's modulus of microcrystalline glass by sound waves.
[0183] In this application, the crystal phase, crystallinity and average grain size of the microcrystalline glass or chemically strengthened microcrystalline glass are confirmed by XRD testing. Specifically:
[0184] (1) XRD test: The glass-ceramics or chemically strengthened glass-ceramics of the present application is crushed and ground into a sample with a particle size of less than 75 μm, and the ground sample is tested using an X-ray diffractometer to obtain an XRD diffraction peak curve and XRD diffraction data. The X-ray diffractometer used in the present application is Shimadzu XRD-6100, the target material is copper, 2θ=10°-50°, the scanning speed is 0.2° / min, the operating voltage is 40 kV, and the operating current is 30 mA.
[0185] (2) Determination of crystalline phase: XRD diffraction data were analyzed using Jade software (JADE Standard 8.6) to determine the crystalline phase in the sample.
[0186] (3) Determination of crystallinity (also known as total crystalline content): The XRD test results (RAW format) are imported into the Jade software for fitting and calculation to determine the crystallinity of the sample. Specifically, the ratio of the fitted crystalline phase peak area to the fitted total peak area is recorded as the crystallinity of the sample.
[0187] (4) Determination of average grain size (or also called average crystal size): The average grain size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the wavelength of the X-ray, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW format file output by the XRD instrument is curve fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), and the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average grain size in the sample.
[0188] In this application, with reference to the national standard "GB / T 7962.12-2010 Test Method for Colorless Optical Glass Part 12: Spectral Transmittance", a haze meter is used to test the transmittance and b value of the microcrystalline glass of this application. Specifically, the haze meter is used to test the transmittance and b value of 5 microcrystalline glass pieces of the same batch to light of different wavelengths. The average value of the b values measured for the 5 microcrystalline glass pieces is taken as the b value result of the microcrystalline glass. The average value of the transmittance of the 5 microcrystalline glass pieces under 550nm wavelength light is taken as the transmittance result of the microcrystalline glass under 550nm wavelength light. The haze meter used in the test of this application is a Konica Minolta spectrophotometer CM-3600A in Japan, the light receiving optical system is transmission, the light splitting mode is a plane refractive grating, the wavelength range is 360nm-740nm, the wavelength spacing is 10nm, the illumination light source is a pulse xenon lamp × 4, the ambient temperature of the instrument is 24℃, and the air humidity is 40%.
[0189] In the present application, Shimadzu's UV-2600 ultraviolet-visible spectrophotometer is also used to test the transmittance curve of the microcrystalline glass or chemically strengthened microcrystalline glass under the wavelength light in the visible light wavelength range.
[0190] Density test: In this application, the electronic density balance SD-200L of Japan ALFAMIRAGE is used to test the density of microcrystalline glass.
[0191] Refractive index test: In this application, the refractive index of microcrystalline glass was tested using Abbe refractometer WYA-2WAJ produced by Shanghai Lichen Bangxi Instrument Technology Co., Ltd., China.
[0192] Thermal expansion softening point test: The sample is made into a cylinder with a diameter of 5.5mm and a length of 20mm, and the sample is tested using a thermal expansion instrument LINSEIS L75VD1000 to output a thermal expansion test curve. The temperature corresponding to the peak position of the curve is the thermal expansion softening point temperature of the sample.
[0193] Crystallization upper limit temperature test: break the substrate glass into small pieces, then put them into the long quartz tank and fill them up. Set the temperature range of the gradient furnace model JKZC-XJY01, such as the temperature range of 1050℃-1225℃, and take at least 6 temperature points from high to low in each temperature range. After the gradient furnace reaches the preset temperature range, put the long quartz tank with the sample into the gradient furnace, so that the 6 temperature points correspond to the glass samples at 6 positions in the long quartz tank, and place the long quartz tank in the gradient furnace at a constant temperature for 60-70 minutes, and then take out the long quartz tank. Use a microscope or magnifying glass to observe the glass samples at different positions in the long quartz tank. If the glass sample is devitrified or foggy, it is determined that the glass sample at that location is crystallized. If the glass sample is completely transparent, it is determined that the glass sample at that location is not crystallized. The crystallization upper limit temperature range is between the temperature point corresponding to the completely transparent sample and the temperature point corresponding to the adjacent devitrified or fogged sample, and the average value of the two temperature points is taken as the crystallization upper limit temperature. If all or none of the glass samples in the long quartz tank crystallize within the temperature range set by the gradient furnace, the temperature range of the gradient furnace is reset to measure the crystallization upper limit temperature of the glass sample.
[0194] In the present application, M(K2O) is the mass percentage of K2O on the surface of the chemically strengthened glass-ceramics. M(Na2O) is the mass percentage of Na2O on the surface of the chemically strengthened glass-ceramics.
[0195] Test method of M(K2O): The K element content on the surface of the chemically strengthened microcrystalline glass is measured by X-ray fluorescence spectrometer (XRF), and then the mass percentage of K2O on the surface is calculated. The calculation method is: surface K2O mass percentage = (surface K element content × relative molecular mass of K2O) / (relative atomic mass of K element × 2). It should be understood that the surface K element content = K element mass / total element mass, and the total element mass = total oxide mass. The equipment model of the X-ray fluorescence spectrometer (XRF) used is Thermo Scientific ARL PERFORM'X, the target material is Rh (rhodium), the light tube voltage is 40kV, the current is 60mA, the collimator is 0.15, the crystal is LiF200, the detector is FPC, the test range is a circle with a diameter of 29mm, and the test method adopts the X_UQ method in the OXSAS analysis software.
[0196] The test method of M(Na2O): The surface Na content in the chemically strengthened microcrystalline glass is measured by X-ray fluorescence spectrometer (XRF), and then the mass percentage of the surface Na2O is calculated. The calculation method is: surface Na2O mass percentage = (surface Na content × relative molecular mass of Na2O) / (relative atomic mass of Na element × 2). It should be understood that the surface Na content = Na element mass / total element mass, and the total element mass = total oxide mass. The X-ray fluorescence spectrometer (XRF) used is Thermo Scientific ARL PERFORM'X, the target material is Rh (rhodium), the light tube voltage is 30kV, the current is 80mA, the collimator is 0.40, the crystal is AxO3, the detector is FPC, the test range is a circle with a diameter of 29mm, and the test method adopts the X_UQ method in the OXSAS analysis software.
[0197] In this application, the XRF instrument is tested using a non-standard test, and the concentration of elements or their oxides with atomic numbers 6 and below in the chemically strengthened microcrystalline glass is not tested. The mass percentage of K2O on the surface of the chemically strengthened microcrystalline glass = the mass of K2O / the total mass of the oxides, and the mass percentage of Na2O on the surface of the chemically strengthened microcrystalline glass = the mass of Na2O / the total mass of the oxides, wherein the oxides include SiO2, Al2O3, ZrO2, Na2O, K2O, P2O5 and other oxides that can be accurately tested by XRF, and do not include the content of oxides that cannot be accurately tested by XRF, such as B2O3 and Li2O.
[0198] In the present application, M'(K2O) is the mass percentage of K2O on the surface of the chemically strengthened glass-ceramic after the two main surfaces of the chemically strengthened glass-ceramic are thinned by 3 μm. M'(Na2O) is the mass percentage of Na2O on the surface of the chemically strengthened glass-ceramic after the two main surfaces of the chemically strengthened glass-ceramic are thinned by 3 μm. The test method of M'(K2O) and M'(Na2O) refers to the test method of M(K2O) and M(Na2O).
[0199] Average sandpaper drop height test: In this application, the sum of the sandpaper drop heights measured for each of the multiple chemically strengthened glass-ceramics samples in the same embodiment or the same comparative example is divided by the number of samples measured, and the value obtained is recorded as the average sandpaper drop height of the tested chemically strengthened glass-ceramics, which is used to characterize the drop damage resistance of the chemically strengthened glass-ceramics. The drop damage resistance here is obtained by using uniform sandpaper testing, which can simulate the application scenario of chemically strengthened glass-ceramics falling onto a ground with relatively uniform roughness.
[0200] Specifically, at least 10 samples were taken from each batch for testing, and the average sandpaper drop height was
[0201] Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample test.
[0202] Among them, the test method for the sandpaper drop height of a single sample is:
[0203] Step 1: Stick 80-grit sandpaper on the lower surface of the 181g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;
[0204] Step 2: Place the chemically strengthened glass-ceramic sample to be tested directly under the model machine, with the chemically strengthened glass-ceramic sample facing the sandpaper, specifically, with the main surface of the chemically strengthened glass-ceramic facing the sandpaper. Make the model machine fall from a certain drop height to impact the chemically strengthened glass-ceramic sample directly under the model machine. If the chemically strengthened glass-ceramic sample does not break, increase the drop height of the model machine in a certain pattern, and make the model machine continue to fall, impacting the chemically strengthened glass-ceramic sample directly under the model machine, until the chemically strengthened glass-ceramic sample breaks. For example, the drop height of the model machine starts from 0.4m, and the sample is dropped once. If the sample does not break, the drop height of the model machine is increased by 0.1m, and it falls again. Repeat the above process until the chemically strengthened glass-ceramic sample breaks;
[0205] Step 3: The last drop height of the chemically strengthened microcrystalline glass sample before it breaks is recorded as its anti-sandpaper drop height. For example, if the drop height is increased by 0.1m each time, when the drop height of the sample is 0.5m when it breaks, the anti-sandpaper drop height of the sample is 0.4m.
[0206] t 强化 :In the embodiment of the present application, the glass-ceramic sample to be strengthened is placed in a corresponding salt bath environment for chemical strengthening. During the strengthening period, the glass-ceramic sample is taken out at regular intervals, and its |CT_AV|, DOL_0, and T are tested by SLP-2000. Then, the formula
[0207]
[0208] Calculate the CT_LD value at that moment. When the CT_LD value reaches the maximum value, the required strengthening time is t 强化 , the test will be placed in the corresponding salt bath environment to strengthen the glass 强化 Stress data of chemically strengthened glass obtained after 3 0.5 min.
[0209] Relation A: In this application, the relation A is the stress characteristic value obtained after the glass-ceramic sample is strengthened in the corresponding salt bath environment for a period of time, which is the ratio of the stress integral of the compressive stress layer from the main surface of the chemically strengthened glass-ceramic sample to the depth DOL_0 along the thickness direction to DOL_0. In the embodiment, the glass-ceramic sample to be strengthened is placed in the corresponding salt bath environment for chemical strengthening. 强化 After a certain time, the prepared chemically strengthened glass-ceramics sample is taken out, and the corresponding stress curve and stress data such as DOL_0 are obtained through SLP-2000 testing. The A value of the chemically strengthened glass-ceramics sample in the corresponding salt bath environment can be obtained by integrating and calculating the stress curve.
[0210] |K 0.5×DOL_0 |: Draw a tangent line at a depth of t=0.5×DOL_0 from the main surface of the chemically strengthened glass-ceramics on the stress curve measured by SLP-2000, calculate the slope of the tangent line, and take the absolute value.
[0211] Without being limited by any theory, when a glass-ceramic with a high lithium content and lithium disilicate as the main crystal phase is chemically strengthened in a molten salt bath, especially in a high-temperature molten salt bath, a large number of irregular cracks / cracks are easily formed on the surface of the chemically strengthened glass-ceramic. These cracks / cracks exist on the surface of the chemically strengthened glass-ceramic. Please refer to Figure 2 and Figure 4 , with a depth of 10μm to 100μm, hereinafter referred to as "surface cracking". The "surface cracking" problem of chemically strengthened microcrystalline glass will greatly reduce the drop damage resistance and mechanical strength of chemically strengthened microcrystalline glass. More seriously, it may even cause the surface of chemically strengthened microcrystalline glass to fail directly due to too many cracks / cracks and cannot be used.
[0212] Without being bound by theory, the inventors found that if the surface compressive stress generated by the microcrystalline glass during the chemical strengthening process is too concentrated while the internal tensile stress is more dispersed, it will easily cause a large stress difference between the inside and outside of the matrix. The surface where the stress is too concentrated will "break", causing "surface cracking", and ultimately causing the prepared chemically strengthened microcrystalline glass to have the problem of "surface cracking".
[0213] Without being bound by any theory, the inventors have discovered that when chemically strengthening glass-ceramics with a high lithium content and lithium disilicate as the main crystalline phase to prepare chemically strengthened glass-ceramics with desired properties, the compatibility between the glass composition and the stress distribution structure is very important. If the two are not compatible, the problem of "surface cracking" of the chemically strengthened glass-ceramics will easily occur, resulting in a significant reduction in the mechanical strength performance of the chemically strengthened glass-ceramics. When the glass-ceramics of a specific composition is matched to a suitable and superior stress distribution structure, not only can the problem of "surface cracking" of the chemically strengthened glass-ceramics be overcome, but also the high mechanical strength performance of the chemically strengthened glass-ceramics can be ensured.
[0214] When chemically strengthening glass-ceramics with a high lithium content and lithium disilicate as the main crystalline phase, the compatibility of the glass composition and its chemical strengthening process is very important. If the compatibility of the two is poor, the more compatible stress distribution structure cannot be obtained, and the chemically strengthened glass-ceramics with the desired performance cannot be obtained.
[0215] In order to improve the problem of "surface cracking" that microcrystalline glass with high lithium content and lithium disilicate as the main crystal phase is prone to after chemical strengthening treatment, a chemically strengthened microcrystalline glass with high lithium content, lithium disilicate as the main crystal phase, specific composition and specific stress distribution structure is provided. The chemically strengthened microcrystalline glass not only does not have the problem of "surface cracking", but also has high mechanical strength performance.
[0216] As described above, in some embodiments of the present application, a chemically strengthened glass-ceramic is provided, wherein the main crystalline phase of the chemically strengthened glass-ceramic is a lithium disilicate crystalline phase; the crystallinity of the chemically strengthened glass-ceramic is not less than 65%; and the Li2O content at the center of the chemically strengthened glass-ceramic is not less than 11% in terms of the mass percentage of the oxide;
[0217] The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside; the chemically strengthened glass-ceramics satisfies the following relationship:
[0218]
[0219] B=A-83989×n(ZrO2) 2 +2526.5×n(ZrO2), 130≤B≤180, preferably, 135≤B≤180, more preferably 135≤B≤175;
[0220] Where t is the depth from the main surface of the chemically strengthened glass-ceramics, CS(t) is the compressive stress value at the depth t, is the stress integral of the compressive stress layer from the main surface of the chemically strengthened glass-ceramics to DOL_0, in MPa·μm;
[0221] DOL_0 is the depth of the compressive stress layer, in μm;
[0222] In relational formula A, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained. The unit does not participate in the calculation;
[0223] n(ZrO2) is the molar percentage content of ZrO2 at the center of the chemically strengthened glass-ceramics;
[0224] In relational expression B, the numerical value of relational expression A and the numerical value of the molar percentage content of ZrO2 are substituted into the calculation to obtain the calculation result, and the unit is not involved in the calculation.
[0225] The present application makes a high-lithium-content microcrystalline glass with a specific composition and lithium disilicate as the main crystal phase meet specific stress characteristics after chemical strengthening treatment. In particular, the relationship A between the molar percentage content of ZrO2 in the microcrystalline glass and the stress characteristics meets specific requirements (that is, meets the range requirements of the aforementioned relationship B). This can not only effectively overcome the problem of "surface cracking" of the chemically strengthened microcrystalline glass, but also ensure that the chemically strengthened microcrystalline glass has high mechanical strength properties, and thus ensure that the chemically strengthened microcrystalline glass has excellent damage resistance.
[0226] When the value of relational expression B exceeds the upper limit, the chemically strengthened microcrystalline glass obtained will experience "surface cracking"; when the value of relational expression B is lower than the lower limit, the chemically strengthened microcrystalline glass obtained cannot obtain the ideal stress effect, its stress level is low, and its mechanical properties and strength properties are poor.
[0227] In some embodiments, the value of relational expression B may be: 130.00, 135.00, 140.00, 145.00, 150.00, 155.00, 160.00, 165.00, 170.00, 175.00, 180.00, 144.41, 149.14, 151.82, 157.96, 159.24, 161.80, 166.00, 148.9 9, 165.83, 168.65, 170.67, 163.85, 155.53, 136.18, 155.43, 172.09, 147.01, 147.17, 165.17, 164.24 or 166.69, or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0228] In some embodiments of the present application, the value of the relational expression A satisfies: 120≤A≤250, preferably, 130≤A≤240, and more preferably, 130≤A≤235. By making the chemically strengthened glass-ceramics satisfy the relational expression A, it is beneficial for the chemically strengthened glass-ceramics to obtain a desired high stress level, thereby facilitating ensuring that the chemically strengthened glass-ceramics has high mechanical strength properties.
[0229] In some embodiments, the value of relational expression A may be: 120.00, 125.00, 130.00, 135.00, 140.00, 145.00, 150.00, 155.00, 160.00, 165.00, 170.00, 175.00, 180.00, 185.00, 190.00, 195.00, 200.00, 205.00, 210.00, 215.00, 220.00, 225.00, 230.00, 235.00, 240.00, 245.00, 250.0 0, 150.39, 155.13, 157.80, 163.95, 165.23, 167.78, 171.98, 130.02, 148.08, 153.52, 157.87, 150.70, 161.51, 200.59, 217.59, 234.24, 208.06, 207.14, 220.07, 224.21 or 226.66, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0230] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: C=A-|CT_AV|, 30≤C≤90, preferably, 30≤C≤85, and more preferably, 30≤C≤80, wherein |CT_AV| is the absolute value of the average tensile stress, in MPa. By making the chemically strengthened glass-ceramics satisfy the relationship C, it helps to overcome the problem of "surface cracking" of the obtained chemically strengthened glass-ceramics, and helps to ensure that the chemically strengthened glass-ceramics have high mechanical strength properties. When the value of the relationship C exceeds the upper limit, the obtained chemically strengthened glass-ceramics will experience "surface cracking"; and when the value of the relationship C is lower than the lower limit, the obtained chemically strengthened glass-ceramics cannot obtain the ideal stress effect, its stress level is low, and its mechanical properties and strength properties are poor.
[0231] In some embodiments, the value of relationship C can be: 30.00, 35.00, 40.00, 45.00, 50.00, 55.00, 60.00, 65.00, 70.00, 75.00, 80.00, 85.00, 90.00, 33.97, 40.28, 37.3, 41.41, 47.67, 42.93, 45.51, 45.77, 52.74, 53.28, 51.42, 52.28, 37.27, 64.74, 70.95, 77.45, 57.85, 52.49, 67.32, 66.26 or 64.31, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required properties of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the chemically strengthened glass-ceramics having the desired properties of the present application can be obtained.
[0232] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies the following relationship: 2≤|K 0.5×DOL_0 |≤6, preferably, 2.5≤|K 0.5×DOL_0 |≤5.5, more preferably, 3≤|K 0.5×DOL_0 |≤5, where |K 0.5×DOL_0 |The absolute value of the slope of the stress curve when the depth from the main surface of the chemically strengthened microcrystalline glass is t = 0.5 × DOL_0. By making the chemically strengthened microcrystalline glass satisfy the above relationship, it is helpful to overcome the problem of "surface cracking" of the obtained chemically strengthened microcrystalline glass and to ensure that the chemically strengthened microcrystalline glass has high mechanical strength. When |K 0.5×DOL_0 When the value of | exceeds the upper limit, the chemically strengthened glass-ceramics will experience "surface cracking"; and when |K 0.5×DOL_0 When the value of | is lower than the lower limit, the chemically strengthened glass-ceramics obtained cannot obtain the ideal stress effect, its stress level is low, and its mechanical properties and strength properties are poor.
[0233] In some embodiments, the relationship |K 0.5×DOL_0The value of | may be: 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 3.088, 3.154, 3.105, 3.241, 3.085, 3.208, 3.309, 2.958, 3.224, 3.647, 3.057, 3.464, 3.354, 4.587, 4.244, 4.216, 4.485, 4.454 or 4.324, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0234] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0≤M(K2O)≤1.5%, 5%≤M(Na2O)≤25%; M(K2O) is the mass percentage of K2O on the surface of the chemically strengthened glass-ceramics, and M(Na2O) is the mass percentage of Na2O on the surface of the chemically strengthened glass-ceramics.
[0235] In some embodiments, M(KO) may be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0236] In some embodiments, M(Na2O) can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5% or 25%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required properties of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the chemically strengthened glass-ceramics having the desired properties of the present application can be obtained.
[0237] In some embodiments of the present application, after the two main surfaces of the chemically strengthened microcrystalline glass are thinned by 3 μm each, the obtained thinned chemical microcrystalline glass satisfies: the mass percentage of K2O M'(K2O) on the surface of the chemical microcrystalline glass and the mass percentage of Na2O M'(Na2O) on the surface of the chemical microcrystalline glass are: 0≤M'(K2O)≤0.5%, 4.0%≤M'(Na2O)≤20%.
[0238] In some embodiments, M'(K2O) may be 0, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0239] In some embodiments, M'(Na2O) may be 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5% or 20%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0240] It should be understood that the chemically strengthened glass-ceramics of the present application is made of glass-ceramics after chemical strengthening treatment, and the mass percentages of Na2O and K2O on the surface of the chemically strengthened glass-ceramics are different from the mass percentages of Na2O and K2O on the surface of the chemically strengthened glass-ceramics after thinning the two main surfaces of the chemically strengthened glass-ceramics by 3 μm in the thickness direction. This is because the glass-ceramics undergoes ion exchange during the chemical strengthening process (for example, Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced, and the surface of the microcrystalline glass is in direct contact with the salt bath, with less obstruction from the glass matrix, and a greater surface exchange rate, forcing larger alkali metal ions (e.g., Na + or K+ ) can enter it more easily, but as the ion exchange proceeds, the internal ions undergo ion exchange, the higher the resistance of the glass matrix is, the more difficult it is to proceed. Therefore, compared with the chemically strengthened microcrystalline glass-ceramics after thinning the two main surfaces by 3μm along the thickness direction, the mass percentage of Na2O and K2O on the surface of the thinned chemically strengthened microcrystalline glass-ceramics, the mass percentage of Na2O and K2O on the surface of the unthinned chemically strengthened microcrystalline glass-ceramics is higher.
[0241] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0.20≤DOL_0 / T≤0.25, preferably, 0.21≤DOL_0 / T≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and T is the thickness of the chemically strengthened glass-ceramics. By making the depth of the compressive stress layer and the thickness of the chemically strengthened glass-ceramics satisfy an appropriate proportional relationship, it is beneficial to ensure that the chemically strengthened glass-ceramics is in a better stress distribution state, and further facilitate the improvement of the mechanical strength performance of the stress structure.
[0242] In some embodiments, the value of DOL_0 / T in the chemically strengthened glass-ceramics may be 0.20 to 0.23 or 0.21 to 0.22. In some embodiments, the value of DOL_0 / T in the chemically strengthened glass-ceramics may be 0.20, 0.21, 0.22, 0.23, 0.24 or 0.25, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0243] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 90 μm ≤ DOL_0 ≤ 160 μm, preferably, 100.00 μm ≤ DOL_0 ≤ 160.00 μm, wherein DOL_0 is the depth of the compressive stress layer. By making the chemically strengthened glass-ceramics have an appropriate DOL_0, it is possible to prevent the sudden cracks generated when blunt or sharp objects impact or pierce directly from penetrating the compressive stress area to reach the tensile stress area, causing the chemically strengthened glass-ceramics to break, thereby being more conducive to improving the energy of the chemically strengthened glass-ceramics to offset the crack propagation, thereby ensuring that the chemically strengthened glass-ceramics has excellent damage resistance, such as excellent drop damage resistance.
[0244] In some embodiments, the DOL_0 of the chemically strengthened glass-ceramics may be 100.00 μm, 105.00 μm, 110.00 μm, 115.00 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 110.54 μm, 109.75 μm, 111.42 μm, 110.75 μm, 114.2 μm, 111.9 μm, 113.24 μm, 105.74 μm, 107.56 μm, 107.96 μm, 110.78 μm, 108.98 μm, 109.87 μm, 107.04 μm, 107.62 μm, 109.78 μm, 110.42 μm, 112.85 μm, 106.99 μm, 107.67 μm or 110.42 μm, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0245] The thickness T of the chemically strengthened glass-ceramics described in the present application is not particularly limited. For example, in some embodiments of the present invention, the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics are plate-shaped. Optionally, the thickness T of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 0.35 to 1.0 mm, preferably 0.4 to 0.7 mm; more preferably, the thickness T is 0.45 mm to 0.55 mm. In some embodiments of the present application, the thickness T of the chemically strengthened glass-ceramics described in the present application can be 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. At present, electronic devices often pursue lightness and thinness, believing that the smaller the thickness, the lighter the weight, and the better the optical effect. The present application can make the chemically strengthened microcrystalline glass product as thin as possible while ensuring the strength, so as to meet the requirements of lightness and thinness of electronic devices.
[0246] The present application facilitates obtaining chemically strengthened microcrystalline glass products with high stress levels by making the chemically strengthened microcrystalline glass satisfy appropriate stress characteristics, thereby facilitating the improvement of mechanical strength properties by the stress characteristics, while ensuring that there is no "surface cracking" problem on the surface of the chemically strengthened microcrystalline glass, and making the chemically strengthened microcrystalline glass satisfy excellent damage resistance.
[0247] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 100MPa≤CS_50≤300MPa, preferably, 110MPa≤CS_50≤250MPa, and more preferably, 110MPa≤CS_50≤240MPa, wherein CS_50 refers to the compressive stress value at a depth of 50μm from the main surface of the chemically strengthened glass-ceramics.
[0248] In some embodiments, the CS_50 of the chemically strengthened glass-ceramics can be 100.00MPa, 110.00MPa, 120.00MPa, 130.00MPa, 140.00MPa, 150.00MPa, 160.00MPa, 170.00MPa, 180.00MPa, 190.00MPa, 200.00MPa, 210.00MPa, 220.00MPa, 230.00MPa, 240.00MPa, 250.00MPa, 260.00MPa, 270.00MPa, 280.00MPa, 290.00MPa, 300.00MPa, 158.56MPa, 168. 85MPa, 168.41MPa, 180.27MPa, 195.42MPa, 170.2MPa, 188.74MPa, 113.52MPa, 153.44MPa, 143.55MPa, 147.58MPa, 153.89MPa, 184.21MPa, 207.1MPa, 216.95MPa, 246.54MPa, 223.64MPa, 229.67MPa, 223.5MPa, 239.75MPa or 244.85MPa, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0249] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 80.00MPa≤|CT_AV|≤200.00MPa, preferably, 80.00MPa≤|CT_AV|≤170.00MPa, and more preferably, 80.00MPa≤|CT_AV|≤160.00MPa, wherein |CT_AV| is the absolute value of the average tensile stress.
[0250] In some embodiments, the |CT_AV| of the chemically strengthened glass-ceramics can be 80.00 MPa to 160.00 MPa, 100.00 MPa to 160.00 MPa, 100.00 MPa to 125.00 MPa, 105.00 MPa to 120.00 MPa, 100.00 MPa to 150.00 MPa, or 110.00 MPa to 115.00 MPa. In some embodiments, the |CT_AV| of the chemically strengthened glass-ceramics may be 80 MPa, 85 MPa, 90 MPa, 100.00 MPa, 110.00 MPa, 120.00 MPa, 125.00 MPa, 130.00 MPa, 135.00 MPa, 140.00 MPa, 150.00 MPa, 160.00 MPa, 170.00 MPa, 180.00 MPa, 190.00 MPa, 200.00 MPa, 116.42 MPa, 114.85 MPa, 120.5 MPa, 122.54 MPa, 117. 56MPa, 124.85MPa, 126.47MPa, 84.25MPa, 95.34MPa, 100.24MPa, 106.45MPa, 98.42MPa, 124.24MPa, 135.85MPa, 146.64MPa, 156.79MPa, 150.21MPa, 154.65MPa, 152.75MPa, 157.95MPa or 162.35MPa, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0251] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 40000.00MPa / mm≤CT_LD≤100000.00MPa / mm, preferably, 47000.00MPa / mm≤CT_LD≤95000.00MPa / mm, wherein CT_LD refers to the tensile stress linear density. Controlling the CT_LD of the chemically strengthened glass-ceramics to a relatively large value, for example, not less than 40000MPa / mm, is conducive to ensuring that the tensile stress stored inside the chemically strengthened glass-ceramics is sufficiently dense, and thus is conducive to ensuring that it has a high surface stress level, ensuring that it can obtain excellent damage resistance, such as excellent drop damage resistance, to meet market demand.
[0252] In some embodiments, the CT_LD of the chemically strengthened glass-ceramics may be 55000MPa / mm to 92000MPa / mm, 58000MPa / mm to 90000MPa / mm, 56000MPa / mm to 94000MPa / mm, or 57000MPa / mm to 93000MPa / mm. In some embodiments, the CT_LD of the chemically strengthened glass-ceramics may be 40000MPa / mm, 45000MPa / mm, 50000MPa / mm, 55000MPa / mm, 60000MPa / mm, 65000MPa / mm, 66000MPa / mm, 67000MPa / mm, 68000MPa / mm, 69000MPa / mm, 70000MPa / mm, 71000MPa / mm, 72000MPa / mm, 73000MPa / mm, 74000MPa / mm, 75000MPa / mm, 76000MPa / mm, 77000MPa / mm, 78000MPa / mm, 79000MPa / mm, 80000MPa / mm, 81000MPa / mm, 82000MPa / mm, 83000MPa / mm, 84000MPa / mm, 85000MPa / mm, 86000MPa / mm, 87000MPa / mm, 88000MPa / mm, 89000MPa / mm, 90000MPa / mm, 91000MPa / mm, 92000MPa / mm, 93000MPa / mm, 94000 2000MPa / mm, 74000MPa / mm, 76000MPa / mm, 78000MPa / mm, 80000MPa / mm, 85000MPa / mm, 90000MPa / mm, 95000MPa / mm, 100000MPa / mm, 64943.73MPa / mm, 64430.85MPa / mm, 66795.56MPa / mm, 68254. 78MPa / mm, 63858.59MPa / mm, 68967.14MPa / mm, 69184.15MPa / mm, 48615.62MPa / mm, 54320.92MP a / mm, 56952.36MPa / mm, 59279.88MPa / mm, 55516.75MPa / mm, 69639MPa / mm, 77684.46MPa / mm, 835 14.41MPa / mm, 87940.38MPa / mm, 83865.25MPa / mm, 84840.99MPa / mm, 87379.11MPa / mm, 89924.09MPa / mm or 90643.25MPa / mm, or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0253] It should be understood that the chemically strengthened glass-ceramics of the present application are made of glass-ceramics subjected to chemical strengthening treatment, and the composition at the center of the chemically strengthened glass-ceramics is the same or substantially the same as the composition of the glass-ceramics. Compared with the glass-ceramics before the chemical strengthening treatment, the composition at the surface of the glass-ceramics after the chemical strengthening treatment may be different from the composition of the glass-ceramics before the chemical strengthening treatment. This is because ion exchange occurs during the chemical strengthening treatment. During the ion exchange, a type of alkali metal ion (e.g., Li+) at the surface of the glass-ceramics in the newly formed glass-ceramics is + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced. However, in an embodiment, the glass composition and phase assembly at or near the depth or thickness center of the microcrystalline glass product will still have the composition and phase assembly of the newly formed microcrystalline glass. That is, in the present application, the composition (e.g., the composition of the tensile stress layer) and phase assembly at the center of the chemically strengthened microcrystalline glass are the same or substantially the same as those of the microcrystalline glass that has not been chemically strengthened.
[0254] In the present application, the glass-ceramics used to prepare chemically strengthened glass-ceramics can be obtained by heat treating a substrate glass. The composition of the substrate glass is the same or substantially the same as that of the glass-ceramics in terms of the molar percentage or mass percentage of the oxide.
[0255] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, in terms of the molar percentage of the oxides, includes: SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 3%, ZrO2: 1% to 6%, Li2O: 24% to 32%. By adjusting and controlling the content range of each oxide component to meet a specific glass composition, it is beneficial to obtain a microcrystalline glass that meets a specific crystal phase structure, and it is beneficial to obtain a chemically strengthened microcrystalline glass that meets a specific stress structure.
[0256] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured in molar percentage of oxides, further includes: SrO: 0% to 3%, and / or, Na2O: 0% to 4%, and / or, K2O: 0% to 2%, and / or, CaO: 0% to 5%, and / or, B2O3: 0% to 1%, and / or, Ta2O5: 0% to 1%, and / or, BaO: 0% to 3%, and / or, MgO: 0% to 3%, and / or, ZnO: 0% to 3%, and / or, Y2O3: 0% to 1%, and / or, La2O3: 0% to 1%, and / or, Yb2O3: 0% to 1%.
[0257] It can be understood that the measurement method of the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be transformed by conversion. For example, the above-mentioned measurement method based on the molar percentage of the oxide can be converted into the mass percentage of the oxide.
[0258] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured in mass percentage of oxides, includes: SiO2: 55% to 75%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 3% to 12%, and Li2O: 11% to 20%.
[0259] In some embodiments of the present application, the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured in mass percentage of oxides, further includes: SrO: 0% to 6%, and / or, Na2O: 0% to 4%, and / or, K2O: 0% to 2%, and / or, CaO: 0% to 5%, and / or, B2O3: 0% to 1%, and / or, Ta2O5: 0% to 2%, and / or, BaO: 0% to 6%, and / or, MgO: 0% to 3%, and / or, ZnO: 0% to 3%, and / or, Y2O3: 0% to 2%, and / or, La2O3: 0% to 2%, and / or, Yb2O3: 0% to 4%.
[0260] In the present application, SiO2 is a glass network forming body oxide, which is an indispensable component of the glass network structure. At the same time, SiO2 is also an important component of the main crystalline phase lithium disilicate (Li2Si2O5) crystalline phase. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, which is conducive to ensuring the precipitation of the desired content of lithium disilicate crystalline phase, but excessive SiO2 will increase the viscosity of the substrate glass, making the glass melting more difficult, thereby reducing the formability of the substrate glass. Therefore, in order to meet the glass formability requirements and achieve the desired crystallization effect of the present application, and then obtain the desired microcrystalline glass or chemically strengthened microcrystalline glass products of the present application, in the present application, the molar percentage content of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 58% to 66%, or the mass percentage content of SiO2 is 55% to 75%.
[0261] In some embodiments, the molar percentage of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 58% to 66%, 60.5% to 64.5%, 60% to 65% or 60.5% to 64%, measured as a molar percentage of the oxide. In some embodiments, in terms of the molar percentage of oxide, the molar percentage of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 60.92%, 60.94%, 61.15%, 61.16%, 61.43%, 61.72%, 61.82%, 62.58%, 62.77%, 63.16%, 63.39% or 63.86%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0262] In some embodiments, the mass percentage of SiO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 55% to 75%, 60% to 71%, 62% to 68%, or 63% to 71%, calculated as the mass percentage of oxides. In some embodiments, the mass percentage of SiO2 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 65.8 6%, 70.54%, 69.11%, 68.06%, 70.78%, 67.86%, 66.67%, 65.63%, 66.06%, 63.50%, 63.96%, 64.45%, 65.47% or 63.31%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0263] In the present application, Al2O3 is an optional component, and the addition of an appropriate amount of Al2O3 helps to promote the exchange of ions during the chemical strengthening process to a certain extent. However, excessive Al2O3 will increase the viscosity of the glass and easily lead to the precipitation of other crystalline phases, such as petalite, which affects the crystalline structure of the microcrystalline glass. Therefore, in the present application, in order to meet the desired crystalline structure and enable the microcrystalline glass or chemically strengthened microcrystalline glass to obtain the desired performance, the molar percentage content of Al2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3.5%, or the mass percentage content of Al2O3 is 0% to 6%.
[0264] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of Al2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 1.14%, 1.22%, 1.23%, 1.37%, 1.38%, 1.4%, 1.42%, 1.43% or 1.44%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0265] In some embodiments, in terms of the mass percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the mass percentage of Al2O3 can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 2.7%, 2.64%, 2.63%, 2.33%, 2.58%, 2.53%, 2.52%, 2.51%, 2.42%, 2.43%, 2.45%, 2.08% or 2.15%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0266] In the present application, P2O5 is a glass-forming oxide, which exists in the network structure as a phosphorus-oxygen tetrahedron [PO4]. P2O5 appears preferentially during the heat treatment process, first causing the glass to phase-segregate and form an amorphous precursor phase Li3PO4, and then using Li3PO4 as a non-uniform nucleation point, crystalline phases such as lithium silicate grow by adhering to the amorphous Li3PO4. With the increase of the P2O5 content, the number of non-uniform nucleation points increases, and the grains with Li3PO4 as the nucleation point are effectively refined, which is beneficial to improving the overall transmittance of microcrystalline glass, the uniformity of the glass and reducing the b value. However, when the P2O5 content is too much, it is easy to generate more Li3PO4 crystals, so that the Li2O content of lithium silicate is insufficient, which leads to the substrate glass being easy to precipitate quartz crystals, resulting in a decrease in the transmittance of microcrystalline glass and a decrease in the overall optical uniformity of microcrystalline glass. When the P2O5 content is too little, the size of the precipitated crystals is too large, which is easy to cause the glass to lose transparency. Therefore, in order to achieve the desired crystallization effect of the present application and make the microcrystalline glass or chemically strengthened microcrystalline glass obtain the desired performance, the molar percentage content of P2O5 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 1% to 3%, or the mass percentage content of P2O5 is 2% to 8%.
[0267] In some embodiments, the molar percentage of P2O5 in the composition of the substrate glass, the composition of the microcrystalline glass, or the composition at the center of the chemically strengthened microcrystalline glass, measured as a molar percentage of the oxide, can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 1.51%, 1.74%, 1.83%, 1.84%, 1.85%, 1.86%, 1.87%, 1.89% or 1.92%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0268] In some embodiments, the mass percentage of P2O5 in the composition of the substrate glass, the composition of the microcrystalline glass, or the composition at the center of the chemically strengthened microcrystalline glass, measured by the mass percentage of the oxide, can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 4.66%, 5.01%, 4.89%, 4.46%, 3.98%, 4.79%, 4.72%, 4.67%, 4.68%, 4.49%, 4.65%, 4.49%, 4.52% or 4.56%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0269] In the present application, ZrO2 is an intermediate oxide in the formation of glass. An appropriate amount of ZrO2 can improve the chemical stability of glass, increase the hardness of glass, and the scratch and drop resistance of glass. At the same time, due to the high cation charge and strong field strength of ZrO2, it has a greater accumulation effect on the glass structure, and is also often used as a nucleating agent in microcrystalline glass. The greater the ZrO2 content, the greater the A value that can be tolerated by lithium disilicate microcrystalline glass without "surface cracking" during the chemical strengthening process, and the more ideal the stress effect produced. However, when the ZrO2 content is high, the optical properties of microcrystalline glass are poor. Therefore, in order to meet the requirements of glass formability and achieve the strength effect expected in the present application, the molar percentage content of ZrO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 1% to 6%, or the mass percentage content of ZrO2 is 3% to 12%.
[0270] In some embodiments, the molar percentage of ZrO2 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, %, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 1.44%, 1.89%, 2.18%, 2.34%, 2.36%, 3.23%, 4.47%, 4.57%, 4.59%, 4.61% or 4.66%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0271] In some embodiments, the mass percentage of ZrO2 in the composition of the substrate glass, the composition of the microcrystalline glass, or the composition at the center of the chemically strengthened microcrystalline glass, measured by the mass percentage of the oxide, can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 7.07%, 3.26%, 4.24%, 4.85%, 5.40%, 5.20%, 7.16%, 10.15%, 10.12%, 9.73%, 10.07%, 9.52%, 9.80% or 9.88%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0272] In the present application, Li2O is a necessary component and a network exo-oxide formed by glass. It can not only improve the viscosity of the glass, promote the melting and clarification of the glass liquid, but also is one of the main components for forming lithium disilicate crystals. At the same time, Li2O can also provide alkali metal lithium ions for ion exchange with large radius ions of the molten salt bath, which is an important factor affecting the stress level that can be obtained by chemically strengthened microcrystalline glass. However, excessive Li2O may cause the stability of the glass crystallization process to deteriorate, and even precipitate other undesirable crystalline phases, which deteriorates the optical properties of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired crystal phase structure, optical properties and mechanical strength properties, the molar percentage content of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 24% to 32%, or the mass percentage content of Li2O is 11% to 20%.
[0273] In some embodiments, the molar percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass, measured as a molar percentage of the oxide, can be 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 27.54%, 29.25%, 29.38%, 29.52%, 29.8%, 30.22%, 30.4%, 30.44%, 30.81% or 31.51%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0274] In some embodiments, the mass percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 11.5%, 12.5%, 13.5%, 14.5%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 11.5%, 11.5%, 12.5%, 13.5%, 13.5%, 14.5%, 15.5%, 16%, 16.5%, 20%, 16.15%, 16.70%, 16.44%, 14.85%, 17.50%, 16.61%, 16.35%, 15.73%, 15.71%, 15.10%, 15.63%, 15.11% or 15.21%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0275] In the present application, Na2O is an optional component and a network exosome oxide. An appropriate amount of Na2O can provide free oxygen, improve the viscosity of the glass, promote the melting and clarification of the glass liquid, and adjust the chemical strengthening rate. However, excessive Na2O will not only reduce the crystallinity of the microcrystalline glass, but also affect the chemical strengthening effect. Therefore, in order to ensure that the microcrystalline glass or chemically strengthened microcrystalline glass meets the desired structure and obtains the desired performance, the molar percentage content of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 4%, or the mass percentage content of Na2O is 0% to 4%.
[0276] In some embodiments, the molar percentage of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, , 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0277] In some embodiments, the mass percentage of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.34%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1 .9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0278] In the present application, K2O is an oxide outside the glass network and is one of the optional components. An appropriate amount of K2O can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, but too much K2O will affect the network structure of the glass, and affect the optical properties, thermal stability, chemical stability, mechanical strength and weather resistance of the glass. Therefore, in order to ensure that the microcrystalline glass or chemically strengthened microcrystalline glass meets the desired structure and obtains the desired performance, the molar percentage content of K2O in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 2%, or the mass percentage content of K2O is 0% to 2%.
[0279] In some embodiments, the molar percentage of K2O in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0280] In some embodiments, the mass percentage of K2O in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.46%, 0.5, 0.6%, 0.7%, 0.78%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0281] In the present application, CaO is an optional component of the network outer oxide formed by glass. An appropriate amount of CaO helps to reduce the high temperature viscosity of the glass and increase the density of the glass, but an excessive amount of CaO will shorten the material properties of the glass and increase its brittleness. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of CaO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 5%, or the mass percentage content of CaO is 0% to 5%.
[0282] In some embodiments, in terms of the molar percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the molar percentage of CaO can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 0.92% or 2.67%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0283] In some embodiments, in terms of the mass percentage of oxide, in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics, the mass percentage of CaO can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 0.92% or 2.7%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0284] In the present application, BaO is an optional component and is an alkaline earth metal oxide. An appropriate amount of BaO can play a role in regulating the glass phase composition in microcrystalline glass, which helps to increase the density of microcrystalline glass and increase its Young's modulus. However, excessive BaO will deteriorate the optical properties of microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of BaO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3%, or the mass percentage content of BaO is 0% to 6%.
[0285] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of BaO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 0.91%, 1.38% or 1.83%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0286] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of BaO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 3.76%, 4.85% or 2.43%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0287] In the present application, SrO is an alkaline earth metal oxide as an optional component. An appropriate amount of SrO can play a role in regulating the glass phase composition in microcrystalline glass, which helps to increase the density of microcrystalline glass and increase its Young's modulus. At the same time, it is also beneficial to reduce the thermal expansion softening point of microcrystalline glass, which is beneficial for hot bending of microcrystalline glass into 3D curved microcrystalline glass. However, excessive SrO will deteriorate the optical properties of microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage of SrO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3%, or the mass percentage of SrO is 0% to 6%.
[0288] In some embodiments, the molar percentage of SrO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 0.91%, 0.92%, 1.38%, 1.42% or 1.83%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0289] In some embodiments, the mass percentage of SrO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 2.68%, 2.57%, 1.64% or 3.33%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0290] In the present application, MgO is an optional component. An appropriate amount of MgO can play a role in regulating the glass phase composition in the microcrystalline glass. However, excessive MgO will affect the growth of crystals and the crystalline structure of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage of MgO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3%, or the mass percentage of MgO is 0% to 3%.
[0291] In some embodiments, the molar percentage of MgO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3% or 1.83%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0292] In some embodiments, the mass percentage of MgO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3% or 1.32%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0293] In the present application, ZnO is one of the optional components as a network intermediate. An appropriate amount of ZnO can combine with free oxygen to adjust the glass structure, and can remain in the glass phase of the microcrystalline glass to increase the glass viscosity, but excessive ZnO will affect the growth of crystals and the crystalline phase structure of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of ZnO in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 3%, or the mass percentage content of ZnO is 0% to 3%.
[0294] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of ZnO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 0.54% or 1.67%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0295] In some embodiments, in terms of the molar percentage of oxide, the molar percentage of ZnO in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.81%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 0.54% or 2.45%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0296] In the present application, B2O3 is an optional component, and an appropriate amount of B2O3 can be used as a flux and / or softener to help improve the molding and hot bending effects of the glass, but excessive B2O3 will cause the crystallization process to be uncontrollable, resulting in the deterioration of the optical properties of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of B2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 1%, or the mass percentage content of B2O3 is 0% to 1%.
[0297] In some embodiments, the molar percentage of B2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.46% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0298] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of B2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.55%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0299] In the present application, the selective addition of an appropriate amount of Y2O3, La2O3, Ta2O5 or Yb2O3 helps to increase the density of the microcrystalline glass and increase its Young's modulus, but it may also increase the refractive index of the microcrystalline glass and reduce the optical properties of the microcrystalline glass. Therefore, in order to obtain microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired optical properties and mechanical strength properties, the molar percentage content of Y2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass is 0% to 1%, and / or the molar percentage content of La2O3 is 0% to 1%, and / or the molar percentage content of Ta2O5 is 0% to 1%, and / or the molar percentage content of Yb2O3 is 0% to 1%, or the mass percentage content of Y2O3 is 0% to 2%, and / or the mass percentage content of La2O3 is 0% to 2%, and / or the mass percentage content of Ta2O5 is 0% to 2%, and / or the mass percentage content of Yb2O3 is 0% to 4%.
[0300] In some embodiments, the molar percentage of Y2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0301] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of Y2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or 0.83%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0302] In some embodiments, the molar percentage of La2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0303] In some embodiments, the mass percentage of La2O3 in the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or 1.18%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the desired performance of the present application can be obtained.
[0304] In some embodiments, the molar percentage of Ta2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.46% or 1%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0305] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of Ta2O5 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or 1.44%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0306] In some embodiments, the molar percentage of Yb2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.46% or 1% in terms of the molar percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0307] In some embodiments, in terms of the mass percentage of oxide, the mass percentage of Yb2O3 in the composition of the substrate glass or the composition of the glass-ceramics or the composition at the center of the chemically strengthened glass-ceramics can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5%, 3%, 3.5%, 4% or 3.12%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0308] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, and more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20, wherein n(SiO2) and n(Li2O) are respectively the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics.
[0309] It should be noted that the content relationship formulas for each oxide in this application are substituted into each formula based on the content percentage of the oxide in moles, and the molar unit does not participate in the calculation of the formula. By adjusting the content of each oxide to meet a specific content relationship, it is beneficial to obtain a microcrystalline glass or chemically strengthened microcrystalline glass that meets the desired mechanical strength properties.
[0310] In some embodiments, the value of n(SiO2) / n(Li2O) may be 2, 2.1, 2.2, 2.3, 2.4, 2.01, 2.03, 2.07, 2.08, 2.09, 2.10 or 2.28, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0311] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 90%≤n(SiO2)+n(Li2O)≤96%, preferably, 90%≤n(SiO2)+n(Li2O)≤95%, wherein n(SiO2) and n(Li2O) are respectively the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics.
[0312] In some embodiments, the value of n(SiO2)+n(Li2O) can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 90.17%, 90.19%, 90.31%, 90.4%, 90.41%, 90.81%, 91.24%, 91.62%, 92.16%, 93.38%, 93.39%, 94.26% or 94.9%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0313] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 20%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, preferably, 25%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, wherein n(Li2O), n(ZrO2), and n(CaO) are respectively the molar percentage contents of Li2O, ZrO2, and CaO at the center of the chemically strengthened glass-ceramics.
[0314] In some embodiments, the value of 2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO) can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 29.39%, 29.77%, 30.05%, 42.65%, 43.99%, 50.6%, 52.02%, 52.88% or 56.88%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0315] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0%≤
[0316] n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤1%, preferably, 0%≤
[0317] n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤0.7%, where n(Y2O3), n(La2O3), n(Ta2O5), n(Yb2O3)
[0318] They are respectively the molar percentage contents of Y2O3, La2O3, Ta2O5 and Yb2O3 at the center of the chemically strengthened glass-ceramics.
[0319] In some embodiments, the value of n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3) can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or 0.46%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0320] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0%≤
[0321] n(SrO)+n(BaO)+n(CaO)+n(MgO)≤3%, preferably, 0%≤n(SrO)+n(BaO)+n(CaO)+n(MgO)≤2.7%, wherein n(SrO), n(BaO), n(CaO), n(MgO) are the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened glass-ceramics, respectively.
[0322] In some embodiments, the value of n(SrO)+n(BaO)+n(CaO)+n(MgO) may be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 0.2%, 0.92%, 1.38%, 1.42%, 1.83% or 2.67%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0323] In some embodiments of the present application, the chemically strengthened glass-ceramics satisfies: 0≤
[0324] n(SrO) / [n(SrO)+n(BaO)+n(CaO)+n(MgO)]≤1, wherein n(SrO), n(BaO), n(CaO), and n(MgO) are respectively the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened glass-ceramics.
[0325] In some embodiments, the value of n(SrO) / [n(SrO)+n(BaO)+n(CaO)+n(MgO)] can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0326] In the present application, "the main crystalline phase is a lithium disilicate crystalline phase" or other similar expressions means that the mass of the lithium disilicate crystalline phase accounts for more than 80 mass percent (mass % or wt %) of all crystalline phases of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics according to the embodiments of the present application. In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the mass of the lithium disilicate crystalline phase accounts for 80wt% to 100wt% of all crystalline phases, preferably, in all crystalline phases of the glass-ceramics or chemically strengthened glass-ceramics, the mass of the lithium disilicate crystalline phase accounts for 85wt% to 100wt%. In some embodiments, in all crystalline phases of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the mass proportion of the lithium disilicate crystalline phase can be 80wt%, 80.5wt%, 81wt%, 81.5wt%, 82wt%, 82.5wt%, 83wt%, 83.5wt%, 84wt%, 84.5wt%, 85wt%, 85.5wt%, 86wt%, 86.5wt%, 87wt%, 87.5wt%, 88wt%, 88.5wt%, 89wt%, 89.5wt%, 90wt%, 95wt% or 100wt%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0327] In the present application, the crystallinity of the glass-ceramics used to prepare chemically strengthened glass-ceramics does not change significantly after chemical strengthening treatment to obtain chemically strengthened glass-ceramics, that is, the crystallinity of the glass-ceramics is similar to or basically the same as the crystallinity of the chemically strengthened glass-ceramics.
[0328] In some embodiments of the present application, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics is not less than 65%, preferably, the crystallinity is not less than 70%, preferably, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics is 70% to 90%, and more preferably, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics is 70% to 87%. The higher the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the more conducive it is to obtain high mechanical strength properties and high damage resistance. However, if the crystallinity is too high, it is easy to affect the chemical strengthening effect of the glass-ceramics, resulting in an extension of the chemical strengthening time for preparing chemically strengthened glass-ceramics with a high stress level, and it is also easy to affect the optical properties of the glass-ceramics. In the present application, by making the glass-ceramics meet the desired crystallinity, it is conducive to making the chemically strengthened glass-ceramics prepared also meet the desired crystallinity, and it is more conducive to obtaining chemically strengthened glass-ceramics that meet the desired high mechanical strength properties, high damage resistance and excellent optical properties.
[0329] In some embodiments, the crystallinity of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 65%, 70%, 72%, 74%, 76%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 79.85 ... 5%, 86.82%, 84.25%, 76.8%, 80.4%, 79.65%, 80.42%, 76.7%, 76.6%, 76.6%, 73.64%, 74.85%, 70.69%, 71.95% or 70.4%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0330] In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, the average grain size does not exceed 100 nm, preferably, the average grain size does not exceed 50 nm, and more preferably, the average grain size is 15 to 30 nm. A suitable average grain size is conducive to the glass-ceramics having both excellent optical properties and high intrinsic strength, while if the average grain size is too high, the glass-ceramics is prone to devitrification. In the present application, by making the glass-ceramics or chemically strengthened glass-ceramics meet the appropriate average grain size, it is conducive to ensuring that the glass-ceramics or chemically strengthened glass-ceramics achieve excellent mechanical strength properties and excellent optical properties.
[0331] In some embodiments, the average grain size of the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics can be 100nm, 50nm, 40nm, 35nm, 30nm, 25nm, 20nm, 15nm, 10nm, 23.7nm, 26.8nm, 23.2nm, 19.6nm, 19.5nm, 24.5nm, 24.2nm, 22.8nm, 23nm, 24.6nm, 24.8nm, 26nm, 25.5nm or 25.6nm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0332] In some embodiments of the present application, in the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics, non-limiting examples of other possible crystalline phases include: petalite crystalline phase, and / or, lithium phosphate crystalline phase. In some embodiments, the mass percentage of the petalite crystalline phase contained in the glass-ceramics or chemically strengthened glass-ceramics is less than or equal to 10%, preferably, the mass percentage of the petalite crystalline phase in the glass-ceramics or chemically strengthened glass-ceramics is less than or equal to 5%, and more preferably, the glass-ceramics or chemically strengthened glass-ceramics do not contain petalite crystalline phase. By controlling the precipitation of other crystalline phases (such as petalite crystalline phase), it is more conducive to ensuring that the lithium disilicate crystalline phase forms a desired interlocking structure, thereby ensuring that the glass-ceramics or chemically strengthened glass-ceramics obtain high mechanical strength properties, excellent optical properties and excellent damage resistance.
[0333] In some embodiments of the present application, when the thickness does not exceed 0.7 mm, the b value of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic is less than 1.0, preferably, the b value is less than 0.80, and more preferably, the b value is ≤ 0.60. It should be understood that in the present application, after the glass-ceramic is chemically strengthened to obtain the chemically strengthened glass-ceramic, its optical properties will not change significantly, that is, the b value, transmittance, etc. of the glass-ceramic are similar to or substantially the same as the b value, transmittance, etc. of the chemically strengthened glass-ceramic. In the present application, the b value refers to the optical b value measured under the D65 light source. The present application uses Konica Minolta CM-3600A to test the b value in transmittance mode, and b(D65) is shown in the result. The smaller the b value, the better the display effect of the glass-ceramic can be ensured. When the b value is too large, the glass-ceramic will have an unexpected color, resulting in its display effect failing to meet the application requirements of the display cover glass.
[0334] In some embodiments, the b value of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 1.0, 0.8, 0.9, 0.70, 0.65, 0.60, 0.55, 0.50, 0.45, 0.40, 0.35, 0.30, 0.25, 0.20, 0.39, 0.32, 0.49, 0.41, 0.56, 0.41, 0.47, 0.51 or 0.52, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics or chemically strengthened glass-ceramics with the desired performance of the present application can be obtained.
[0335] In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550nm, the transmittance of the glass-ceramics or chemically strengthened glass-ceramics is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.27%. Glass-ceramics or chemically strengthened glass-ceramics that meet this transmittance can ensure good light transmittance and good transparency, and are suitable for use in display screens that require display effects. The "visible light wavelength range" here refers to light with a wavelength of 360nm-740nm.
[0336] In some embodiments, for light of 550nm wavelength, the transmittance of the glass-ceramics used to prepare chemically strengthened glass-ceramics or chemically strengthened glass-ceramics can be 85%, 90%, 91%, 92%, 90.76%, 90.76%, 90.76%, 90.76%, 90.76%, 90.76%, 90.76%, 90.76%, 90.31%, 90.59%, 91%, 90.94%, 90.63%, 90.65%, 90.4%, 90.46%, 90.46%, 90.29%, 90.37%, 90.27%, 90.3%, 90.35%, or can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the glass-ceramics or chemically strengthened glass-ceramics with the required performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass having the desired performance of the present application can be obtained.
[0337] In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics have a Young's modulus greater than 100 GPa, preferably, a Young's modulus greater than 105 GPa, and more preferably, a Young's modulus of 110 GPa to 130 GPa. It should be understood that in the present application, after the glass-ceramics is chemically strengthened to obtain chemically strengthened glass-ceramics, its Young's modulus does not decrease, that is, when the Young's modulus of the glass-ceramics is greater than 100 GPa, the Young's modulus of the chemically strengthened glass-ceramics obtained should also be greater than 100 GPa. A higher Young's modulus is conducive to ensuring that the chemically strengthened glass-ceramics has high mechanical strength and high damage resistance.
[0338] In some embodiments, the Young's modulus of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics can be 100 GPa, 101 GPa, 102 GPa, 103 GPa, 104 GPa, 105 GPa, 106 GPa, 107 GPa, 108 GPa, 109 GPa, 110 GPa, 111 GPa, 112 GPa, 113 GPa, 114 GPa, 115 GPa, 116 GPa, 117 GPa, 118 GPa, 119 GPa, 120 GPa, 125 GPa, 128 GPa, 130 GPa, 118.6 GPa, 116.5 GPa, 116.1 GPa, 115.63 GPa, 116.52 GPa, 117.64 GPa, 118.8 GPa, 117.073 GPa, 114.27 GPa, 114.27 GPa, 113.3 GPa, 114.52 GPa, 120 GPa, 119.3 GPa or 118.95 GPa, or it can be a value in the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the required performance of the present application can be obtained.
[0339] In some embodiments of the present application, the density of the glass-ceramics or chemically strengthened glass-ceramics used to prepare the chemically strengthened glass-ceramics is 2.51 g / cm 3 ~2.65g / cm 3 In some embodiments, the density of the glass-ceramics used to prepare the chemically strengthened glass-ceramics or the chemically strengthened glass-ceramics may be 2.51 g / cm 3 , 2.52g / cm 3 , 2.53g / cm 3 , 2.54g / cm 3 , 2.55g / cm 3, 2.56g / cm 3 , 2.57g / cm 3 , 2.58g / cm 3 , 2.59g / cm 3 , 2.60g / cm 3 , 2.61g / cm 3 , 2.62g / cm 3 , 2.63g / cm 3 , 2.64g / cm 3 or 2.65g / cm 3 , or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass or chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0340] In some embodiments of the present application, the refractive index of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic is ≤1.60, preferably, the refractive index is 1.54-1.60. In some embodiments, the refractive index of the glass-ceramic or chemically strengthened glass-ceramic used to prepare the chemically strengthened glass-ceramic can be 1.54, 1.55, 1.56, 1.57, 1.58, 1.59 or 1.60, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramic or chemically strengthened glass-ceramic with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramic or chemically strengthened glass-ceramic with the required performance of the present application can be obtained.
[0341] In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the glass-ceramics or chemically strengthened glass-ceramics used to prepare chemically strengthened glass-ceramics are of equal thickness or unequal thickness. Those skilled in the art can choose according to demand. The "unequal thickness" here refers to the glass-ceramics or chemically strengthened glass-ceramics containing at least two parts with different thicknesses.
[0342] In some embodiments of the present application, a sandpaper drop resistance test is performed on the chemically strengthened glass-ceramics, and the sandpaper used is 80-mesh sandpaper. When the thickness does not exceed 0.70 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.0 m, preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.2 m, and more preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.6 m. The larger the measured average sandpaper drop resistance height value, the better the drop damage resistance of the chemically strengthened glass-ceramics.
[0343] In some embodiments, when the chemically strengthened microcrystalline glass is dropped on 80-grit sandpaper, the average sandpaper drop height can be 1.0m, 1.1m, 1.11m, 1.12m, 1.13m, 1.14m, 1.15m, 1.16m, 1.17m, 1.18m, 1.19m, 1.2m, 1.25m, 1.28m, 1.3m, 1.35m, 1.4m, 1.4 5m, 1.5m, 1.55m, 1.6m, 1.65m, 1.7m, 1.75m, 1.8m, 1.85m, 1.9m, 1.95m, 2.1m, 2.2m, 2.3m, 2.4m, 2.5m or 2m, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the chemically strengthened microcrystalline glass with the performance required by the present application can be obtained.
[0344] After introducing the composition, crystal phase structure and stress structure of chemically strengthened microcrystalline glass, the preparation method of chemically strengthened microcrystalline glass is introduced in detail below.
[0345] In the present application, the preparation process of chemically strengthened microcrystalline glass mainly includes: the preparation process of microcrystalline glass and the chemical strengthening treatment process, and the preparation process of microcrystalline glass mainly includes: the preparation process of substrate glass and the heat treatment process of substrate glass.
[0346] In the present application, the substrate glass can be prepared by a molding method in the prior art, and the present application has no limitation on this. For example, the molding method of the substrate glass can include but is not limited to float, overflow, rolling or casting processes. For example, the substrate glass can be obtained by uniformly mixing the components according to the formula, melting and molding, cooling and annealing.
[0347] Exemplarily, each raw material (industrial conventional raw material) is configured according to the formula ratio, a clarifier is added, and then mixed for a period of time to obtain a uniform raw material mixture. The raw material mixture is placed in a platinum crucible, a platinum rhodium crucible or a furnace, heated to 1450°C to 1700°C, preferably kept warm for 5 hours or more under the melting temperature condition, and then poured into a molding mold for cooling and molding, preferably cooled to about 900°C, and then placed in an annealing furnace for annealing treatment, preferably the annealing temperature is 450°C to 650°C, and the annealing time is preferably 10 to 48 hours, and then cooled to room temperature with the furnace to obtain the substrate glass. Those skilled in the art can select the type and amount of clarifier according to demand, and they do not need to pay creative labor. Further, the clarifier may include but is not limited to one or more of sodium chloride, tin oxide, antimony oxide or arsenic oxide, and the amount of clarifier added may be 0-1wt% of the total amount of each raw material.
[0348] In some embodiments of the present application, the heat treatment process of the substrate glass may include a nucleation treatment and / or a crystallization treatment, preferably a nucleation treatment and a crystallization treatment. In some embodiments, the crystallization treatment includes a one-step crystallization treatment or a two-step crystallization treatment. In some embodiments, in order to prepare curved microcrystalline glass, a two-step crystallization treatment method can be selected. When a two-step crystallization treatment is adopted, the second step crystallization treatment is to heat the crystallized glass raw material obtained by the first step crystallization treatment to a hot pressing temperature, and simultaneously perform a 3D hot bending forming treatment and a second step crystallization treatment. The "crystallized glass raw material" here refers to a glass material with a certain degree of crystallinity, but has not yet reached the crystallinity requirement required for the final sample.
[0349] In some embodiments of the present application, in order to obtain the desired physical and chemical properties of the microcrystalline glass, when the substrate glass is heat treated, a one-step heat treatment may be performed, or two-step or more-step heat treatment may be performed. If a one-step heat treatment is performed, it means that a nucleation treatment (i.e., nucleation treatment) is not performed separately, and a one-step heating is performed directly, and nucleation and crystal growth are performed at a temperature reached in the one-step heating process, which can be understood as a direct crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, including but not limited to the following methods, a first step of nucleation treatment, and a second step of crystallization treatment.
[0350] In some embodiments of the present application, in order to precipitate the desired target crystalline phase in the microcrystalline glass and obtain the desired physical and chemical properties, the substrate glass is subjected to nucleation treatment and crystallization treatment in sequence. Furthermore, when performing the nucleation treatment, the nucleation temperature can be 500-700°C, and the nucleation time can be 10-1440 min; when performing the crystallization treatment, the crystallization temperature can be 600-800°C, and the crystallization time can be 5-1440 min. During the heat treatment process of the nucleation treatment and the crystallization treatment, it is preferred to control the heating rate to be 5-20°C / min, more preferably the heating rate to be 10°C / min, and the cooling rate can be 0.1°C / min-3°C / min.
[0351] In the present application, after heat treatment, those skilled in the art may further perform other conventional steps to obtain a microcrystalline glass sample that meets the desired specifications or requirements, for example, shaping treatment, cutting treatment (e.g., cutting using a multi-wire cutting machine), CNC machining (computer numerical control, i.e., CNC machine tools), thinning treatment, or polishing treatment and the like.
[0352] In some embodiments of the present application, chemically strengthened glass-ceramics that meet desired properties can be prepared by subjecting the aforementioned glass-ceramics to a specific chemical strengthening treatment.
[0353] In some embodiments of the present application, the step of polishing and thinning the prepared chemically strengthened glass-ceramics is also included.
[0354] In the present application, the chemical strengthening treatment, namely the ion exchange method, is performed by immersing the microcrystalline glass in a molten salt bath so that the alkali metal ions with smaller ion radius in the microcrystalline glass are exchanged with the alkali metal ions with larger ion radius in the molten salt bath, thereby forming a compressive stress layer on the surface of the microcrystalline glass and a tensile stress layer inside the microcrystalline glass, thereby obtaining chemically strengthened microcrystalline glass with better mechanical properties.
[0355] In some embodiments of the present application, the chemical strengthening treatment may be performed by a single-step strengthening method or a multi-step strengthening method. The molten salt bath for chemical strengthening treatment is a molten salt bath containing sodium salt and / or potassium salt. Preferably, the molten salt bath of the present application is a mixed molten salt bath containing sodium salt and potassium salt, and the temperature of the molten salt bath is preferably 380°C to 600°C, preferably 430°C to 550°C. In some embodiments of the present application, the concentration of potassium salt in the salt bath is preferably 0wt% to 95wt%, and the concentration of sodium salt is 5wt% to 100wt%, and more preferably a certain amount (e.g., 0.01wt%-0.3wt%) of lithium salt is added to the salt bath. In some embodiments of the present application, the time of the chemical strengthening treatment is preferably 0.1 to 24h. Among them, the sodium salt can be selected from at least one of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate; the potassium salt can be selected from at least one of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the lithium salt can be selected from at least one of lithium nitrate, lithium sulfate, and lithium carbonate, preferably lithium nitrate.
[0356] In the present application, the stress distribution structure of the chemically strengthened glass-ceramics is closely related to the glass-ceramics composition (including oxide composition, crystal phase composition), salt bath composition, salt bath temperature and chemical strengthening treatment time. Only when the glass-ceramics of a specific composition is in a suitable salt bath (suitable composition and suitable temperature) and chemically strengthened for a suitable time, can the prepared chemically strengthened glass-ceramics obtain a specific stress distribution structure, thereby achieving the excellent effect expected to be achieved in the present application.
[0357] The chemically strengthened microcrystalline glass with excellent performance provided in the present application can be used in electronic devices, including but not limited to mobile phones, tablet computers, handheld game consoles, portable digital devices (such as digital cameras), vehicle-mounted central control, electronic whiteboard glass, smart home, smart wear (such as smart bracelets, smart watches, smart glasses), and can also be used in vehicles, aircraft or aircraft, and can also be used in any glass device of chemically strengthened microcrystalline glass required. For example, it can be used for display screens, cover glass, touch screens, glass inner screens or inner frames of electronic devices; for example, it can be used for windshields of vehicles, aircraft or aircraft, such as front windshields or side windshields. For example, it can be used for work surfaces, other surfaces, appliance doors, floor tiles, wall panels or storage containers. Other surfaces can include but are not limited to exterior wall surfaces, stair tread surfaces, column veneers or counter surfaces, etc., and storage containers can include but are not limited to cups, plates, medicine bottles or beverage bottles, etc.
[0358] For example, the chemically strengthened glass-ceramics with excellent performance provided in the present application can be used to manufacture glass devices. The glass devices referred to here can be regular or irregular, and those skilled in the art can manufacture them according to requirements.
[0359] For example, the chemically strengthened microcrystalline glass with excellent performance provided by the present application can be used to manufacture cover glass, and the cover glass can be a display cover, back cover or camera protection cover of an electronic device. For example, the chemically strengthened microcrystalline glass with excellent performance provided by the present application can be used in electronic devices. Fig.15 , Fig.16 , Fig.17 and Fig.18 In an embodiment of the present application, an electronic device is provided, which may be an electronic product such as a mobile phone, a tablet computer, a smart wearable device, etc. The electronic device includes a housing 1 assembled on the outside of the electronic device, and components such as a circuit board and a battery located inside the housing 1. The housing 1 includes a display screen cover 11 assembled on the front side and a back cover 12 assembled on the back side. The display screen cover 11 is covered on the display module 4, wherein the display screen cover 11 and / or the back cover 12 are made of the aforementioned chemically strengthened microcrystalline glass. In an embodiment of the present application, the display screen cover 11 and the back cover 12 may all be made of the aforementioned chemically strengthened microcrystalline glass, or only partially made of the aforementioned chemically strengthened microcrystalline glass. In an embodiment of the present application, the display screen may be a touch display screen, and the display screen cover 11 may be a protective cover provided on the touch display screen. In an embodiment of the present application, the back cover 12 may only cover the back side (and the side away from the display screen) of the electronic device, or may cover the back side and side frame of the electronic device at the same time. Optionally, the back cover 12 may cover all side frames around the electronic device, or may cover part of the side frame.
[0360] In some implementation modes of the present application, Fig.16 As shown, the electronic device also includes a camera assembly 2 located inside the housing 1, and the housing 1 may include a camera protection cover 13, which is covered on the camera assembly 2 to protect the camera assembly 2, and the camera protection cover 13 adopts the aforementioned chemically strengthened microcrystalline glass. In the embodiment of the present application, the camera protection cover 13 may be partially made of the aforementioned chemically strengthened microcrystalline glass, or it may be entirely made of the aforementioned chemically strengthened microcrystalline glass. In the embodiment of the present application, the setting position of the camera protection cover 13 is determined according to the setting position of the camera assembly 2, and it may be located on the front side of the electronic device, or it may be located on the back side of the electronic device. In some embodiments of the present application, the camera protection cover 13 may be a separate structure from the display screen cover 11 or the back cover 12. In other embodiments of the present application, the camera protection cover 13 may also be an integrated structure with the display screen cover 11 or the back cover 12.
[0361] In some embodiments of the present application, Fig.17 As shown, the electronic device further includes a middle frame 3 located between the display module 4 and the housing 1 , and the middle frame 3 may include the aforementioned chemically strengthened microcrystalline glass.
[0362] In the embodiments of the present application, the display screen cover, back cover, camera protection cover, and middle frame in the electronic device may be made of any one of the aforementioned chemically strengthened microcrystalline glass, or any two of them may be made of the aforementioned chemically strengthened microcrystalline glass, or all three may be made of the aforementioned chemically strengthened microcrystalline glass, or all four may be made of the aforementioned chemically strengthened microcrystalline glass.
[0363] In some embodiments of the present application, the display screen cover, back cover, camera protection cover or middle frame in the electronic device may be 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the display screen cover, back cover, camera protection cover or middle frame in the electronic device may be of equal thickness or unequal thickness.
[0364] The technical solution of the present application is further described in detail below in conjunction with the embodiments. The embodiments of the present application described in detail below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0365] Example 1
[0366] 1. Preparation of substrate glass
[0367] The raw materials were configured according to the proportions of the oxides in Table 1. The total mass of the configured raw materials was 1000 g. 5 g of clarifier sodium chloride (NaCl) was added to the configured raw materials. The mixture was then mixed at a speed of 25 r / min for more than 30 minutes using a V-type mixer to obtain a uniform raw material mixture.
[0368] The mixed raw material mixture is transferred to a platinum crucible, and then melted in a platinum-rhodium crucible at 1600℃ for more than 5 hours, and then poured into a molding mold for molding and cooling. When it cools to about 900℃, it is then placed in a 460℃ annealing furnace for annealing for 12 hours, and then cooled to room temperature with the furnace to obtain a base glass brick with a size of approximately 180mm*65mm*24mm.
[0369] 2. Preparation of glass-ceramics
[0370] The base glass brick is subjected to nucleation treatment and crystallization treatment in sequence to prepare a transparent micro-ceramic glass brick. The composition of the prepared micro-ceramic glass is the same as that of the base glass in terms of the molar percentage of oxides, as shown in Table 1. The relationship between the compositions of the micro-ceramic glass is shown in Table 2.
[0371] In order to obtain the microcrystalline glass product of Example 1 of the present application, during the nucleation treatment, the temperature is increased to the nucleation temperature at a heating rate of 10°C / min, the nucleation temperature is 520°C, and the nucleation insulation time is 240min; during the crystallization treatment, the temperature is increased from the nucleation temperature to the crystallization temperature at a heating rate of 10°C / min, the crystallization temperature is 690°C, and the crystallization insulation time is 90min, and then the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain a microcrystalline glass sample brick. The nucleation insulation time here, i.e. the nucleation time, refers to the insulation time after the crystallization furnace is heated to the set nucleation temperature at the set heating rate. The crystallization insulation time here, i.e. the crystallization time, refers to the insulation time after the crystallization furnace is heated to the set crystallization temperature at the set heating rate.
[0372] The obtained microcrystalline glass sample bricks are cut, CNC processed (the CNC instrument model used in this application is: RCG500S), and polished in turn through cold processing to produce microcrystalline glass samples that meet the required specifications and requirements.
[0373] In the specific examples and comparative examples of the present application, the glass-ceramic sample bricks were subjected to the aforementioned cold working treatment to produce glass-ceramic polished sheet samples with a length and width of 50 mm×50 mm and a thickness of 0.50 mm.
[0374] The glass-ceramics samples obtained in Example 1 were tested as follows:
[0375] The crystal phase composition, crystallinity, average crystal size (average grain size), expansion softening point, density, refractive index, Young's modulus, optical b value and transmittance (under 550nm wavelength light) of the microcrystalline glass samples were tested respectively. The results are shown in Table 3.
[0376] 3. Preparation of chemically strengthened glass-ceramics
[0377] The microcrystalline glass polishing sheet obtained above was subjected to a one-step chemical strengthening treatment in a mixed salt at 460° C. The strengthening time was 600 min. The composition of the mixed salt was: the mass ratio of NaNO 3 : KNO 3 : LiNO 3 in the molten salt was 29.99% : 69.98% : 0.03%.
[0378] After the chemical strengthening treatment, the microcrystalline glass sample is taken out and placed on the strengthening furnace body to slowly cool to room temperature, and then the salt wrapped on the surface of the microcrystalline glass is washed off with clean water. After the microcrystalline glass sample is dried, a chemically strengthened microcrystalline glass is obtained. The chemically strengthened microcrystalline glass obtained in Example 1 is tested as follows:
[0379] Ⅰ. Determine whether the chemically strengthened micro-ceramic glass has "surface cracks": If strong light is irradiated on the surface of the chemically strengthened micro-ceramic glass, no cracks are observed on the surface of the glass. Figure 1As shown, or the chemically strengthened microcrystalline glass is placed under an Axiolab5 polarizing microscope, using an LED light source, and magnified 100 times or 200 times, no cracks are observed on the glass surface, such as Figure 3 , it means that the chemically strengthened microcrystalline glass has no "surface cracking" problem in appearance, and it is recorded as "qualified" in appearance. If strong light is irradiated on the surface of chemically strengthened microcrystalline glass, bright cracks are observed, such as Figure 2 As shown, or the chemically strengthened microcrystalline glass is placed under an Axiolab 5 polarizing microscope, using an LED light source, and magnified 100 times or 200 times, and cracks are observed on the glass surface, such as Figure 4 , indicating that the chemically strengthened microcrystalline glass has a "surface cracking" problem and is recorded as "unqualified" in appearance.
[0380] The effect of the chemically strengthened microcrystalline glass of Example 1 under strong light irradiation is as follows Figure 1 As shown in FIG. 1 , the main surface and the cross section along the thickness direction of the chemically strengthened microcrystalline glass are shown in the morphology under a microscope (magnified 200 times). Figure 3 and Figure 5 As shown, it can be seen that there are no bright cracks, and there are no irregular cracks inside or on the surface of the glass.
[0381] II. Stress test: The chemically strengthened microcrystalline glass obtained in each embodiment or comparative example is measured under SLP-2000 stress meter (the light source wavelength used is 518nm, SOC=25.5 (nm / cm) / MPa, the refractive index is set according to the refractive index value of the sample to be tested, and the exposure time is 300μsec) to measure CS_50, DOL_0, |CT_AV|; then the tensile stress line density CT_LD value and the stress integral value of the compressive stress layer from the main surface of the chemically strengthened microcrystalline glass to DOL_0 and the absolute value of the slope of the stress curve when the depth t is 0.5×DOL_0 |K are calculated. 0.5×DOL_0 |, the results are shown in Table 4.
[0382] III. Surface composition test of chemically strengthened glass-ceramics: The mass percentage of K2O and the mass percentage of Na2O on the surface of the chemically strengthened glass-ceramics were tested by XRF, and the results are shown in Table 5. At the same time, the two main surfaces of the prepared chemically strengthened glass-ceramics were polished and thinned by a polishing machine. After the two main surfaces were thinned by 3μm respectively, the thinned chemically strengthened glass-ceramics were obtained. The mass percentage of K2O and the mass percentage of Na2O on the surface of the thinned chemically strengthened glass-ceramics were tested by XRF, and the results are shown in Table 5.
[0383] The transmittance curve of the chemically strengthened microcrystalline glass of Example 1 is as follows: Fig. 9 As shown. Fig. 9It can be seen that in the present application, the chemically strengthened glass-ceramics is transparent in the visible light range and has a high transmittance.
[0384] The XRD pattern of the glass-ceramics of Example 1 is as follows: Fig.10 As shown, the XRD patterns of the glass-ceramics of Example 1 before and after chemical strengthening are as follows Fig.11 As shown. Fig.10 and Fig.11 It can be seen that in the present application, the main crystalline phase in the microcrystalline glass and the chemically strengthened microcrystalline glass is the lithium disilicate crystalline phase, and the crystalline phase structure of the microcrystalline glass does not change significantly before and after the chemical strengthening treatment.
[0385] Example 2-Example 21
[0386] The above methods are respectively carried out with reference to Example 1, except that the glass composition, different process parameters and corresponding test results of each example are shown in Tables 1 to 5, respectively.
[0387] Comparative Example 1-Comparative Example 10
[0388] The above methods are respectively carried out with reference to Example 1, except that the glass composition, different process parameters and corresponding test results of each comparative example are shown in Tables 1 to 5, respectively.
[0389] Among them, the XRD patterns of the glass-ceramics of Comparative Example 5 before and after chemical strengthening are as follows: Fig.12 As shown. Fig.12 It can be seen that in the present application, the main crystalline phase in the microcrystalline glass and the chemically strengthened microcrystalline glass is the lithium disilicate crystalline phase, and the crystalline phase structure of the microcrystalline glass does not change significantly before and after the chemical strengthening treatment.
[0390] Crystallization upper limit temperature test: In order to analyze the industrial mass production feasibility of the microcrystalline glass of the present application, the crystallization upper limit temperatures of the substrate glasses of some embodiments were tested. See Table 3 for details. The crystallization upper limit temperatures of the substrate glasses of the tested embodiments were all between 1000°C and 1100°C, indicating that the microcrystalline glass of the present application is suitable for industrial mass production.
[0391] Expansion softening point test: In order to analyze the 3D hot bending effect of the microcrystalline glass of the present application, the thermal expansion coefficient test curves of the microcrystalline glass in some embodiments were tested, and the expansion softening point was obtained. See Table 3 for details. From the test results, it can be seen that the expansion softening point of the microcrystalline glass of the present application is between 750°C and 830°C, indicating that the microcrystalline glass of the present application is conducive to 3D hot bending molding to prepare 3D curved microcrystalline glass.
[0392]
[0393]
[0394]
[0395]
[0396]
[0397]
[0398]
[0399]
[0400]
[0401]
[0402]
[0403]
[0404] It can be seen from the embodiments and comparative examples of Statement 1-Table 5 above that, compared with the comparative example, by adopting the embodiment scheme of the present application, a high-lithium-content microcrystalline glass with a specific composition and lithium disilicate as the main crystalline phase satisfies specific stress characteristics after chemical strengthening treatment, including making the molar percentage content of ZrO2 in the microcrystalline glass and the stress characteristic relationship A meet specific requirements (that is, meet the range requirements of relationship B), or making the stress characteristic relationship A and the average tensile stress value |CT_AV| meet specific requirements (that is, meet the range requirements of relationship C), or making the stress curve slope |K 0.5×DOL_0 | Meeting specific range requirements can not only effectively overcome the problem of "surface cracking" of the chemically strengthened glass-ceramics, but also ensure that the chemically strengthened glass-ceramics has high mechanical strength properties, thereby ensuring that the chemically strengthened glass-ceramics has excellent damage resistance.
[0405] However, in the schemes of Comparative Examples 1 to 10, the composition and stress structure of the chemically strengthened microcrystalline glass do not meet the specific requirements of the present application, such as not meeting the specific range requirements of Relationship B and Relationship C required to be met by the scheme of the present application. Ultimately, the chemically strengthened microcrystalline glass obtained in the schemes of each comparative example either has the problem of "surface cracking" and cannot meet the appearance requirements or achieve excellent resistance to drop damage performance, or the obtained stress level is too low to obtain the ideal stress effect, and the mechanical properties and strength properties are poor and cannot achieve excellent resistance to drop damage performance.
[0406] For example, the chemically strengthened glass-ceramics prepared in Comparative Examples 1 to 9 were calculated by Relationship B and Relationship C, and it was found that their values exceeded the scope requirements of the technical solution of this application. The final test found that these chemically strengthened glass-ceramics all had the problem of "surface cracking", and when the anti-sandpaper drop test was carried out, the average anti-sandpaper drop height of these chemically strengthened glass-ceramics was less than 0.8m. The chemically strengthened glass-ceramics prepared in Comparative Example 10 were calculated by Relationship B and Relationship C, and it was found that their values were less than the scope requirements of the technical solution of this application. The final test found that although the chemically strengthened glass-ceramics did not have the problem of "surface cracking", when the anti-sandpaper drop test was carried out, the average anti-sandpaper drop height was only 0.9m, which was less than 1m.
[0407] For another example, in Examples 1 to 7, Comparative Examples 5 to 7, and Comparative Example 10, glass-ceramics having the same glass composition and crystal structure are used to prepare chemically strengthened glass-ceramics. However, due to the different values of the stress characteristics and the composition of the prepared chemically strengthened glass-ceramics satisfying the relational expression B and the relational expression C, it is finally found that the chemically strengthened glass-ceramics prepared in Examples 1 to 7 that meet the requirements of the technical solution scope of the present application not only overcome the problem of "surface cracking", but also have an average sandpaper drop resistance of these chemically strengthened glass-ceramics of 1.040 W / m2 when subjected to the sandpaper drop resistance test. The drop heights of the chemically strengthened glass-ceramics obtained in Comparative Examples 5 to 7, which do not meet the requirements of the scope of the technical solution of the present application, are all higher than 1.3m, and the "surface cracking" problem occurs in all of them, and when the sandpaper drop test is carried out, the average sandpaper drop height of these chemically strengthened glass-ceramics is lower than 0.6m, while the chemically strengthened glass-ceramics obtained in Comparative Example 10, which does not meet the requirements of the scope of the technical solution of the present application, does not have the "surface cracking" problem, but when the sandpaper drop test is carried out, the average sandpaper drop height of the chemically strengthened glass-ceramics is lower than 1m. This shows that when chemically strengthening glass-ceramics with high lithium content and lithium disilicate as the main crystalline phase is subjected to chemical strengthening treatment to prepare chemically strengthened glass-ceramics with desired properties, the matching relationship between the glass composition and the stress distribution structure is very important. When the glass-ceramics of a specific composition is matched to a suitable and better stress distribution structure, it can not only overcome the problem of "surface cracking" of the chemically strengthened glass-ceramics obtained, but also ensure that the chemically strengthened glass-ceramics has high mechanical strength properties.
[0408] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A chemically strengthened glass-ceramic, characterized in that: The main crystalline phase of the chemically strengthened glass-ceramics is a lithium disilicate crystalline phase; the crystallinity of the chemically strengthened glass-ceramics is not less than 65%; the Li2O content at the center of the chemically strengthened glass-ceramics is not less than 11% in terms of the mass percentage of oxides; The chemically strengthened glass-ceramics has a compressive stress layer on the surface and a tensile stress layer inside; the chemically strengthened glass-ceramics satisfies the following relationship: B=A-83989×n(ZrO2) 2 +2526.5×n(ZrO2), 130≤B≤180, preferably, 135≤B≤180, More preferably, 135≤B≤175; Where t is the depth from the main surface of the chemically strengthened glass-ceramics, CS(t) is the compressive stress value at the depth t, is the stress integral of the compressive stress layer from the main surface of the chemically strengthened glass-ceramics to DOL_0, in MPa·μm; DOL_0 is the depth of the compressive stress layer, in μm; In relational formula A, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained. The unit does not participate in the calculation; n(ZrO2) is the molar percentage content of ZrO2 at the center of the chemically strengthened glass-ceramics; In relational expression B, the numerical value of relational expression A and the numerical value of the molar percentage content of ZrO2 are substituted into the calculation to obtain the calculation result, and the unit is not involved in the calculation.
2. The chemically strengthened glass-ceramics according to claim 1, characterized in that: The value of the relational expression A satisfies: 120≤A≤250, preferably, 130≤A≤240, and more preferably, 130≤A≤235.
3. The chemically strengthened glass-ceramics according to any one of claims 1 to 2, characterized in that: The chemically strengthened glass-ceramics satisfies the following relationship: C=A-|CT_AV|, 30≤C≤90, preferably, 30≤C≤85, and more preferably, 30≤C≤80, wherein |CT_AV| is the absolute value of the average tensile stress, in MPa.
4. The chemically strengthened glass-ceramics according to any one of claims 1 to 3, characterized in that: The chemically strengthened glass-ceramics satisfies the following relationship: 2.0≤|K 0.5×DOL_0 |≤6.0, where |K 0.5×DOL_0 |The absolute value of the slope of the stress curve when the depth from the main surface of the chemically strengthened micro-ceramic glass is t=0.5×DOL_0.
5. The chemically strengthened glass-ceramics according to any one of claims 1 to 4, characterized in that: The chemically strengthened glass-ceramics meets the following requirements: 0.20≤DOL_0 / T≤0.25, preferably, 0.21≤DOL_0 / T≤0.23, wherein DOL_0 is the depth of the compressive stress layer, and T is the thickness of the chemically strengthened glass-ceramics; and / or, 90.00 μm≤DOL_0≤160.00 μm, preferably, 100.00 μm≤DOL_0≤160.00 μm, wherein DOL_0 is the depth of the compressive stress layer; and / or, 100.00MPa≤CS_50≤300.00MPa, preferably, 110.00MPa≤CS_50≤250.00MPa, more preferably, 110.00MPa≤CS_50≤240.00MPa, wherein CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened microcrystalline glass; and / or, 80.00MPa≤|CT_AV|≤200.00MPa, preferably, 80.00MPa≤|CT_AV|≤170.00MPa, more preferably, 80.00MPa≤|CT_AV|≤160.00MPa, wherein |CT_AV| is the absolute value of the average tensile stress; and / or, 40000.00MPa / mm≤CT_LD≤100000.00MPa / mm, preferably, 47000.00MPa / mm≤CT_LD≤95000.00MPa / mm, wherein CT_LD refers to tensile stress linear density.
6. The chemically strengthened glass-ceramics according to any one of claims 1 to 5, characterized in that: The chemically strengthened microcrystalline glass satisfies: 0≤M(K2O)≤1.5%, 5%≤M(Na2O)≤25%; M(K2O) is the mass percentage of K2O on the surface of the chemically strengthened microcrystalline glass, and M(Na2O) is the mass percentage of Na2O on the surface of the chemically strengthened microcrystalline glass; and / or, After the two main surfaces of the chemically strengthened microcrystalline glass are thinned by 3 μm each, the obtained chemical microcrystalline glass satisfies: the mass percentage of K2O M'(K2O) on the surface of the chemical microcrystalline glass and the mass percentage of Na2O M'(Na2O) on the surface of the chemical microcrystalline glass are: 0≤M'(K2O)≤0.5%, 4.0%≤M'(Na2O)≤20%.
7. The chemically strengthened glass-ceramics according to any one of claims 1 to 6, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, comprises: SiO2: 58% to 66%, Al2O3: 0% to 3.5%, P2O5: 1% to 3%, ZrO2: 1% to 6%, Li2O: 24% to 32%.
8. The chemically strengthened glass-ceramics according to claim 7, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, further comprises: SrO: 0% to 3%, and / or Na2O: 0% to 4%, and / or K2O: 0% to 2%, and / or CaO: 0% to 5%, and / or B2O3: 0% to 1%, and / or Ta2O5: 0% to 1%, and / or BaO: 0% to 3%, and / or MgO: 0% to 3%, and / or ZnO: 0% to 3%, and / or Y2O3: 0% to 1%, and / or La2O3: 0% to 1%, and / or Yb2O3:0%~1%.
9. The chemically strengthened glass-ceramics according to any one of claims 1 to 8, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in molar percentage of oxides, comprises: The molar percentage of SiO2 is 60% to 65%, preferably 60.5% to 64.50%; and / or, The molar percentage of Al2O3 is 0.5% to 3.5%, preferably 1% to 1.5%; and / or, The molar percentage of P2O5 is 1% to 2.8%, preferably 1.20% to 2%; and / or, The molar percentage of ZrO2 is 1% to 5%, preferably 1.4% to 5%; and / or, The molar percentage of Li2O is 24% to 31.6%, preferably 27.5% to 31%; and / or, The molar percentage of Na2O is 0% to 3%, preferably 0% to 1%; and / or, The molar percentage of K2O is 0% to 1%, preferably 0% to 0.7%; and / or, The molar percentage of CaO is 0% to 4%, preferably 0% to 3%; and / or, The molar percentage of BaO is 0% to 2%, preferably 1% to 2%; and / or, The molar percentage of SrO is 0% to 2%, preferably 1% to 2%; and / or, The molar percentage of MgO is 0% to 2%; and / or, The molar percentage of ZnO is 0% to 2%; and / or, The molar percentage of B2O3 is 0% to 0.7%, preferably 0% to 0.5%; and / or, The molar percentage of Y2O3 is 0% to 0.5%, preferably 0% to 0.2%; and / or, The molar percentage of La2O3 is 0% to 0.5%, preferably 0% to 0.2%; and / or, The molar percentage of Ta2O5 is 0% to 0.7%, preferably 0% to 0.5%; and / or, The molar percentage of Yb2O3 is 0% to 0.7%, preferably 0% to 0.5%.
10. The chemically strengthened glass-ceramics according to any one of claims 1 to 9, characterized in that: The chemically strengthened glass-ceramics meets the following requirements: 2.00≤n(SiO2) / n(Li2O)≤2.40, preferably, 2.00≤n(SiO2) / n(Li2O)≤2.30, more preferably, 2.02≤n(SiO2) / n(Li2O)≤2.20, wherein n(SiO2) and n(Li2O) are the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics, respectively; and / or, 90%≤n(SiO2)+n(Li2O)≤96%, preferably, 90%≤n(SiO2)+n(Li2O)≤95%, wherein n(SiO2) and n(Li2O) are respectively the molar percentage contents of SiO2 and Li2O at the center of the chemically strengthened glass-ceramics; and / or, 20%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, preferably, 25%≤2.25×n(Li2O)-8×n(ZrO2)-0.2×n(CaO)≤60%, wherein n(Li2O), n(ZrO2), and n(CaO) are the molar percentage contents of Li2O, ZrO2, and CaO at the center of the chemically strengthened glass-ceramics, respectively; and / or, 0%≤n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤1%, preferably, 0%≤n(Y2O3)+n(La2O3)+n(Ta2O5)+n(Yb2O3)≤0.7%, wherein n(Y2O3), n(La2O3), n(Ta2O5), and n(Yb2O3) are the molar percentage contents of Y2O3, La2O3, Ta2O5, and Yb2O3 at the center of the chemically strengthened glass-ceramics, respectively; and / or, 0%≤n(SrO)+n(BaO)+n(CaO)+n(MgO)≤3%, preferably, 0%≤n(SrO)+n(BaO)+n(CaO)+n(MgO)≤2.7%, wherein n(SrO), n(BaO), n(CaO), n(MgO) are the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened glass-ceramics, respectively; and / or, 0≤n(SrO) / [n(SrO)+n(BaO)+n(CaO)+n(MgO)]≤1, wherein n(SrO), n(BaO), n(CaO), and n(MgO) are respectively the molar percentage contents of SrO, BaO, CaO, and MgO at the center of the chemically strengthened glass-ceramics.
11. The chemically strengthened glass-ceramics according to any one of claims 1 to 6, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in percentage by mass of oxides, comprises: SiO2: 55% to 75%, Al2O3: 0% to 6%, P2O5: 2% to 8%, ZrO2: 3% to 12%, Li2O: 11% to 20%.
12. The chemically strengthened glass-ceramics according to claim 11, characterized in that: Measured in percentage by mass of oxides, the composition at the center of the chemically strengthened glass-ceramics also includes: SrO: 0% to 6%, and / or Na2O: 0% to 4%, and / or K2O: 0% to 2%, and / or CaO: 0% to 5%, and / or B2O3: 0% to 1%, and / or Ta2O5: 0% to 2%, and / or BaO: 0% to 6%, and / or MgO: 0% to 3%, and / or ZnO: 0% to 3%, and / or Y2O3: 0% to 2%, and / or La2O3: 0% to 2%, and / or Yb2O3: 0% to 4%.
13. The chemically strengthened glass-ceramics according to any one of claims 11 or 12, characterized in that: The composition at the center of the chemically strengthened glass-ceramics, measured in percentage by mass of oxides, comprises: The mass percentage of SiO2 is 60% to 71%, preferably 62% to 68%; and / or, The mass percentage of Al2O3 is 1% to 6%, preferably 1% to 3%, more preferably 2% to 3%; and / or, The mass percentage of P2O5 is 3% to 6%, preferably 3.5% to 5.5%; and / or, The mass percentage of ZrO2 is 4% to 11%, preferably 4% to 10%; and / or, The mass percentage of Li2O is 11% to 18%, preferably 12% to 17.5%, more preferably 14% to 17%; and / or, The mass percentage of Na2O is 0% to 2.8%, preferably 0% to 1%; and / or, The mass percentage of K2O is 0% to 1.5%, preferably 0% to 1%; and / or, The mass percentage of CaO is 0% to 3%, preferably 0% to 1%; and / or, The mass percentage of BaO is 0% to 5.5%, preferably 0% to 5%; and / or, The mass percentage of SrO is 0% to 5%, preferably 0% to 3.5%; and / or, The mass percentage of MgO is 0% to 2%; and / or, The mass percentage of ZnO is 0% to 2.5%; and / or, The mass percentage of B2O3 is 0% to 0.8%, preferably 0% to 0.5%; and / or, The mass percentage of Y2O3 is 0% to 1%, preferably 0% to 0.8%; and / or, The mass percentage of La2O3 is 0% to 1.5%, preferably 0% to 1%; and / or, The mass percentage of Ta2O5 is 0% to 1.5%, preferably 0% to 0.5%; and / or, The mass percentage of Yb2O3 is 0% to 3.5%, preferably 0% to 3%.
14. The chemically strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: The chemically strengthened glass-ceramics has a crystallinity of 70% to 90%, more preferably, the chemically strengthened glass-ceramics has a crystallinity of 70% to 87%; and / or, In the chemically strengthened glass-ceramics, the average grain size does not exceed 100 nm, preferably, the average grain size does not exceed 50 nm, and more preferably, the average grain size is 15 nm to 30 nm; and / or, In the chemically strengthened glass-ceramics, the mass of lithium disilicate crystal phase accounts for 80wt% to 100wt% of all crystal phases; and / or, The mass percentage of the petalite crystalline phase in the chemically strengthened glass-ceramics is less than or equal to 10%, preferably less than or equal to 5%, and more preferably, does not contain the petalite crystalline phase.
15. The chemically strengthened glass-ceramics according to any one of claims 1 to 14, characterized in that: When the thickness is not more than 0.70 mm, the b value of the chemically strengthened glass-ceramics is less than 1.0, preferably, the b value is less than 0.8, and more preferably, the b value is ≤ 0.6; and / or, The chemically strengthened glass-ceramics is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass-ceramics is ≥85%, preferably, the transmittance is ≥90%, and more preferably, the transmittance is ≥90.27%.
16. The chemically strengthened glass-ceramics according to any one of claims 1 to 15, characterized in that: The Young's modulus of the chemically strengthened glass-ceramics is greater than 100 GPa, preferably greater than 105 GPa, more preferably 110 GPa to 130 GPa; and / or, The density of the chemically strengthened glass-ceramics is 2.51 g / cm 3 ~2.65g / cm 3 and / or, The refractive index of the chemically strengthened glass-ceramics is ≤1.60, preferably, the refractive index is 1.54 to 1.60; and / or, The thickness T of the chemically strengthened glass-ceramics is 0.35 mm to 1.0 mm, preferably, the thickness T is 0.4 mm to 0.7 mm, and more preferably, the thickness T is 0.45 mm to 0.55 mm; and / or, The chemically strengthened glass-ceramics are 2D, 2.5D, 3D or special-shaped; and / or, The chemically strengthened glass-ceramics have equal thickness or unequal thickness.
17. The chemically strengthened glass-ceramics according to any one of claims 1 to 16, characterized in that: The chemically strengthened glass-ceramics is subjected to a sandpaper drop resistance test, and the sandpaper used is 80 mesh sandpaper. When the thickness does not exceed 0.70 mm, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.0 m, preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.2 m, and more preferably, the average sandpaper drop resistance height of the chemically strengthened glass-ceramics is ≥1.6 m.
18. The chemically strengthened glass-ceramics according to claim 3, characterized in that: The chemically strengthened glass-ceramics shown satisfies: the value of relation A is: 150.39, 155.13, 157.8, 163.95, 165.23, 167.78, 171.98, 130.02, 148.08, 153.52, 157.87, 150.70, 161.51, 200.59, 217.59, 234.24, 208.06, 207.14, 220.07, 224.21 or 226.66; and / or, The value of relational expression B is: 144.41, 149.14, 151.82, 157.96, 159.24, 161.80, 166.00, 148.99, 165.83, 168.65, 170.67, 163.85, 155.53, 136.18, 155.43, 172.09, 147.01, 147.17, 165.17, 164.24 or 166.69; and / or, The values of relational expression C are: 33.97, 40.28, 37.3, 41.41, 47.67, 42.93, 45.51, 45.77, 52.74, 53.28, 51.42, 52.28, 37.27, 64.74, 70.95, 77.45, 57.85, 52.49, 67.32, 66.26 or 64.
31.
19. A cover glass, characterized in that: The cover glass comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
20. An electronic device, characterized in that: The electronic device comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
21. The electronic device according to claim 20, characterized in that: The electronic device includes a housing assembled on the outside of the electronic device, and the housing includes the chemically strengthened micro-ceramic glass according to any one of claims 1 to 18.
22. The electronic device according to claim 21, characterized in that: The housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the chemically strengthened microcrystalline glass according to any one of claims 1 to 18.
23. The electronic device according to claim 21 or 22, characterized in that: The housing includes a back cover assembled on the back side of the electronic device, and the back cover includes the chemically strengthened micro-ceramic glass according to any one of claims 1 to 18.
24. The electronic device according to any one of claims 21 to 22, characterized in that: The electronic device also includes a camera assembly located inside the housing, the housing includes a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover includes the chemically strengthened microcrystalline glass according to any one of claims 1-18.
25. The electronic device according to any one of claims 21 to 24, characterized in that: The electronic device further includes a middle frame, and the middle frame includes the chemically strengthened microcrystalline glass according to any one of claims 1 to 18.
26. A glass device, characterized in that: The glass device comprises the chemically strengthened glass-ceramic according to any one of claims 1 to 18.
Citation Information
Patent Citations
Chemically strengthened microcrystalline glass and strengthening method
CN112608033A
Lithium aluminosilicate microcrystalline glass with internal stress and production method thereof
CN118270982A
Glass ceramic, chemically strengthened glass ceramic, cover plate glass and electronic equipment
CN118290031A
Chemically strengthened microcrystalline glass, cover plate glass, electronic equipment and glass device
CN118702411A
Chemically strengthened lithium disilicate-petalite glass-ceramics
US20200148591A1
Cited By
Glass ceramic, preparation method thereof, electronic equipment cover plate prepared from glass ceramic and electronic equipment cover plate assembly
CN120736800A
Chemically strengthened microcrystalline glass, cover glass plate, electronic device, and glass component
WO2026067404A1
Chemically strengthened microcrystalline glass, cover glass, electronic device, and glass device
WO2026067725A1